Low-color polymers for use in electronic devices
A polyimide film with improved thermal stability and light permeability is achieved by using specific tetracarboxylic acid and diamine components in a non-protonic solvent, addressing rigidity and optical retardation issues in electronic devices.
Patent Information
- Application Number
- JP2022179489
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-09-19
- Filing Date
- 2022-11-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2038-09-11
AI Technical Summary
Conventional polyimide materials used in electronic devices face challenges such as rigidity, high aromaticity, optical retardation, and limited light permeability, which affect their performance in applications like color filters and touch screen panels.
A polyimide film is developed using a high-boiling point non-protonic solvent containing specific tetracarboxylic acid and diamine components with direct chemical bonds between aromatic rings, resulting in a polymer structure with improved thermal stability, reduced optical retardation, and enhanced light permeability.
The new polyimide film exhibits a low thermal expansion coefficient, high glass transition temperature, and excellent mechanical properties, along with reduced yellowing and optical retardation, making it suitable for flexible electronic devices.
Smart Images

Figure 0007623334000016 
Figure 0007623334000017 
Figure 0007623334000001
Abstract
Description
[Technical field]
[0001] Claiming the Benefit of a Prior Application This application claims the benefit of U.S. Provisional Patent Application No. 62 / 560,274, filed Sep. 19, 2017, which is incorporated by reference in its entirety.
[0002] The present disclosure relates to novel polymeric compounds. The present disclosure further relates to methods of preparing such polymeric compounds and electronic devices having at least one layer comprising these materials. [Background technology]
[0003] Materials for use in electronics applications often have strict requirements for their structural, optical, thermal, electronic and other properties. As the number of commercial electronic applications continues to grow, the breadth and specificity of the required properties strongly demands the innovation of materials with new and / or improved properties. Polyimides refer to a class of polymer compounds that have been widely used in a variety of electronic applications. With the right properties, they can serve as flexible replacements for glass in electronic display devices. These materials can serve as components of liquid crystal displays ("LCDs"), where their modest power consumption, light weight and flatness of layers are crucial properties for effective utility. Other uses of electronic display devices that emphasize such parameters include device substrates, substrates for color filter sheets, cover films, touch screen panels and others.
[0004] Some of these components are also important in the construction and operation of organic electronic devices, including organic light-emitting diodes ("OLEDs"). OLEDs are promising for many display applications due to their high power conversion efficiency and wide range of end-user applicability. They are increasingly being used in mobile phones, tablet devices, handheld / laptop computers, and other commercial products. These applications require displays with large amounts of information, full color, and fast video-speed response times, in addition to low power consumption.
[0005] Polyimide films generally have sufficient thermal stability, high glass transition temperatures, and mechanical toughness to merit such use, and polyimides generally do not fog with repeated flexing, making them often preferred over other transparent substrates such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN) for flexible display applications.
[0006] However, the traditional brown color of polyimides precludes their use in some display applications, such as color filters and touch screen panels, due to the emphasis on optical transparency. Furthermore, polyimides are generally rigid, highly aromatic materials whose polymer chains tend to orient in the plane of the film / coating as it is formed. This creates a difference in the parallel and perpendicular refractive index of the film (birefringence), resulting in optical retardation that can adversely affect display performance. If polyimides are to find further use in the display market, solutions are needed to maintain the desired properties while at the same time improving optical transparency and reducing the birefringence that results in the brown color and optical retardation.
[0007] Towards these goals, several materials development strategies have been pursued. Synthetic strategies that disrupt the relatively rigid polymer chain conformation with monomers containing flexible cross-linking units and / or meta-linkages have shown some promise, but polyimides resulting from such syntheses tend to have higher coefficients of thermal expansion (CTE), lower glass transition temperatures (T) and lower thermal expansion coefficients (CTE) than are desirable for many end uses. g ) and / or a low modulus of elasticity. The same property drawbacks often follow synthetic strategies that aim to disrupt the conformation of the polymer chains by the introduction of monomers with bulky side groups.
[0008] Some other strategies have not been as successful in preparing polyimide films that exhibit low color. The use of aliphatic or partially aliphatic monomers, while effective in breaking the long-range conjugation that can result in excessive color, has been found to result in polyimides with reduced mechanical and thermal performance for end use in many electronic devices. The use of dianhydrides with low electron affinity and / or diamines that are weak electron donors has also been attempted. However, such structural modifications may result in unacceptably slow polymerization rates for use in industrial applications.
[0009] Finally, the use of extremely pure monomers, particularly the diamine components of polyimides, has been attempted as a mechanism for reducing the color properties of these films, however the industrial processes involved in this approach to low-color materials are generally cost prohibitive for current commercial electronics applications. Summary of the Invention [Problem to be solved by the invention]
[0010] Thus, there is a continuing need for low-color materials that are suitable for use in electronic devices. [Means for solving the problem]
[0011] A solution containing a polyamic acid in a high boiling aprotic solvent is provided, wherein the polyamic acid comprises one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components is a tetravalent organic group derived from a bent dianhydride or an aromatic dianhydride containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, and at least one of the diamine components is a divalent organic group derived from a bent diamine or an aromatic diamine containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl, and fluoroalkyl.
[0012] Further provided is a polyimide film produced from a solution containing a polyamic acid in a high boiling point aprotic solvent, wherein the polyamic acid comprises one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components being a tetravalent organic group derived from a bent dianhydride or an aromatic dianhydride containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, and at least one of the diamine components being a divalent organic group derived from a bent diamine or an aromatic diamine containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings; R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl, and fluoroalkyl.
[0013] Formula I
[0014] [ka]
[0015] (In the formula, R ais a tetravalent organic radical derived from one or more dianhydrides selected from the group consisting of bent dianhydrides and aromatic dianhydrides containing one or more aromatic tetracarboxylic acid moieties containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- chains or direct chemical bonds between the aromatic rings, and R b is a divalent organic radical derived from one or more diamines selected from the group consisting of benzylidene and aromatic diamines containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl. There is further provided a polyimide film comprising the repeat unit The in-plane coefficient of thermal expansion (CTE) is less than 75 ppm / ℃ from 50℃ to 250℃. Glass transition temperature (T g ) exceeds 250°C for polyimide films cured at 260°C in air, The 1% TGA weight loss temperature is over 450℃. The tensile modulus is 1.5 GPa to 5.0 GPa. The elongation at break exceeds 20%. The optical retardation at 550 nm is less than 20 nm for a 10 μm film, The birefringence at 633 nm is less than 0.002; Haze is less than 1.0%. b * is less than 3, The yellowness index is less than 5; and The average transmittance from 380nm to 780nm exceeds 88%.
[0016] There is further provided a method for preparing a polyimide film, the method being selected from the group consisting of a thermal method and a modified-thermal method, the thermal method comprising the following steps: coating one or more of the polyamic acid solutions disclosed herein onto a substrate; soft baking the coated substrate; treating the soft-baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals. in turn, whereby the polyimide film comprises An in-plane coefficient of thermal expansion (CTE) of less than 75 ppm / °C from 50°C to 250°C; The glass transition temperature (T) of polyimide films cured at 260°C in air or N2 is greater than 250°C. g ), 1% TGA weight loss temperature above 450℃, Tensile modulus of 1.5GPa~5.0GPa, Elongation at break of more than 20% Optical retardation at 550 nm, which is less than 20 nm for a 10 μm film; Birefringence at 633 nm that is less than 0.002; Haze less than 1.0%; b* is less than 3; A yellowness index of less than 5; and Over 88% average transmittance from 380nm to 780nm Shows.
[0017] There is further provided a flexible replacement for glass in electronic devices, wherein the flexible replacement for glass is represented by Formula I
[0018] [ka]
[0019] (In the formula, R a is a tetravalent organic radical derived from one or more dianhydrides selected from the group consisting of bent dianhydrides and aromatic dianhydrides containing one or more aromatic tetracarboxylic acid moieties containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- chains or direct chemical bonds between the aromatic rings, and R b is a divalent organic radical derived from one or more diamines selected from the group consisting of benzylidene and aromatic diamines containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl. It is a polyimide film having the repeating unit:
[0020] Further provided are organic electronic devices, such as, for example, OLEDs, where the organic electronic devices comprise the flexible alternatives to glass disclosed herein.
[0021] The foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as defined in the appended claims.
[0022] Embodiments are illustrated in the accompanying drawings to facilitate understanding of the concepts presented herein. [Brief description of the drawings]
[0023] [Figure 1] Included is an illustration of one example of a polyimide film that can serve as a flexible replacement for glass. [Diagram 2] Included is an illustration of one embodiment of an electronic device that includes a flexible alternative to glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Those skilled in the art will appreciate that objects in the figures are illustrated for simplicity and clarity and have not necessarily been drawn to scale For example, the dimensions of some of the objects in the figures may be exaggerated relative to other objects to help improve understanding of the embodiments.
[0025] As described in detail below, a solution containing a polyamic acid in a high boiling aprotic solvent is provided, wherein the polyamic acid comprises one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components is a tetravalent organic group derived from a bent dianhydride or aromatic dianhydride containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, at least one of the diamine components is a divalent organic group derived from a bent diamine or aromatic diamine containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, and R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl.
[0026] Further provided are one or more polyimide films whose repeat units have the structure of Formula I.
[0027] Further provided are one or more methods for preparing a polyimide film, wherein the polyimide film has a repeat unit of Formula I:
[0028] There is further provided a flexible replacement for glass in electronic devices, wherein the flexible replacement for glass is a polyimide film having a repeating unit of Formula I:
[0029] An electronic device is further provided having at least one layer comprising a polyimide film having a repeating unit of Formula I.
[0030] A number of aspects and embodiments have been described above, and are illustrative only and not limiting. After reading this specification, skilled artisans will appreciate that other aspects and embodiments are possible without departing from the scope of the invention.
[0031] Other features and advantages of any one or more of the embodiments will be apparent from the following detailed description and claims, which begin with definitions and explanations of terms, followed by polyimide films having the repeating unit structure of Formula I, methods for preparing polyimide films, flexible replacements for glass in electronic devices, electronic devices, and finally examples.
[0032] 1. Definitions and Explanations of Terms Before addressing the details of the embodiments described below, a few terms will be defined or explained.
[0033] As used in the "Definitions and Explanations of Terms", R, R a , R b , R', R'', and any other variables are generic and may be the same or different from the variables defined in the formula.
[0034] The term "alignment layer" is intended to mean a layer of organic polymer in a liquid crystal device (LCD) that causes the molecules to align closest to each plate as a result of being rubbed against the LCD glass in one preferred direction during the LCD manufacturing process.
[0035] The term "alkyl" as used herein includes branched and straight chain saturated aliphatic hydrocarbon groups. Unless otherwise specified, the term is also intended to include cyclic groups. Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, isobutyl, secbutyl, tertbutyl, pentyl, isopentyl, neopentyl, cyclopentyl, hexyl, cyclohexyl, isohexyl, and the like. The term "alkyl" further includes both substituted and unsubstituted hydrocarbon groups. In some embodiments, the alkyl group can be mono-, di-, and tri-substituted. An example of a substituted alkyl group is trifluoromethyl. Other substituted alkyl groups are formed from one or more of the substituents described herein. In certain embodiments, the alkyl group has 1-20 carbon atoms. In other embodiments, the group has 1-6 carbon atoms. The term is intended to include heteroalkyl groups. The heteroalkyl group can have 1-20 carbon atoms.
[0036] The term "aprotic" refers to a class of solvents that lack an acidic hydrogen atom and therefore cannot act as a hydrogen donor. Common aprotic solvents include alkanes, carbon tetrachloride (CCl4), benzene, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), and many others.
[0037] The term "aromatic compound" is intended to mean an organic compound that contains at least one unsaturated cyclic group having 4n+2 delocalized pi-electrons. The term is intended to encompass both aromatic compounds having only carbon and hydrogen atoms as well as heteroaromatic compounds in which one or more of the carbon atoms in the cyclic group are replaced by another atom such as nitrogen, oxygen, sulfur, etc.
[0038] The term "aryl" or "aryl group" refers to a moiety derived from an aromatic compound. A group "derived from" a compound refers to a radical formed by the removal of one or more hydrogens ("H") or deuteriums ("D"). An aryl group can have a single ring (monocyclic) or multiple rings (bicyclic or higher) fused together or joined by covalent bonds. A "hydrocarbon aryl" has only carbon atoms in the aromatic rings. A "heteroaryl" has one or more heteroatoms in at least one aromatic ring. In some embodiments, a hydrocarbon aryl group has 6-60 ring carbon atoms, and in some embodiments, 6-30 ring carbon atoms. In some embodiments, a heteroaryl group has 4-50 ring carbon atoms, and in some embodiments, 4-30 ring carbon atoms.
[0039] The term "alkoxy" is intended to mean the group --OR, where R is alkyl.
[0040] The term "aryloxy" is intended to mean the group --OR, where R is aryl.
[0041] Unless otherwise stated, all groups may be substituted or unsubstituted. Optionally substituted groups, such as, but not limited to, alkyl or aryl, may be substituted with one or more substituents, which may be the same or different. Suitable substituents include D, alkyl, aryl, nitro, cyano, -N(R')(R"), halo, hydroxy, carboxy, alkenyl, alkynyl, cycloalkyl, heteroaryl, alkoxy, aryloxy, heteroaryloxy, alkoxycarbonyl, perfluoroalkyl, perfluoroalkoxy, arylalkyl, silyl, siloxy, siloxane, thioalkoxy, -S(O)2-, -C(=O)-N(R')(R"), (R')(R")N-alkyl, (R')(R")N-alkoxyalkyl, (R')(R")N-alkylaryloxyalkyl, -S(O) s -aryl (wherein s=0 to 2) or -S(O) s-heteroaryl, where s=0-2. R' and R" are each independently an optionally substituted alkyl, cycloalkyl, or aryl group. In certain embodiments, R' and R" can form a ring system together with the nitrogen atom to which they are attached. Substituents can also be bridging groups. Any of the foregoing groups with available hydrogens can be deuterated.
[0042] The term "amine" is intended to mean a compound or functional group that contains a basic nitrogen atom with a lone pair of electrons. It refers to the group -NH2 or -NR2, where R is the same or different at each occurrence and can be an alkyl group, an aryl group or a deuterated analogue thereof. The term "diamine" is intended to mean a compound or functional group that contains two basic nitrogen atoms with associated lone pairs of electrons. The term "bent diamine" refers to a compound or functional group in which the two basic nitrogen atoms and associated lone pairs are the same as the corresponding compound or functional group, e.g., m-phenylenediamine.
[0043] [ka]
[0044] is intended to mean diamines that are asymmetrically arranged around the center of symmetry of
[0045] The term "aromatic diamine component" is intended to mean a divalent moiety bonded to two amino groups in an aromatic diamine compound. The aromatic diamine component is derived from an aromatic diamine compound. The aromatic diamine component may also be described as being made from an aromatic diamine compound.
[0046] The term “b * " is the b in the CIELab color space, which represents the yellow / blue opponent color. * Yellow is intended to represent the positive b * The color is represented by a negative b value. * It is represented by the measured b value. *Values can be affected by the solvent, especially since the choice of solvent can affect the color measured on materials exposed to high temperature processing conditions. This can occur as a result of the inherent properties of the solvent and / or properties associated with low levels of impurities contained in various solvents. Particular solvents may provide the desired b value for a particular application. * Often preselected to achieve a certain value.
[0047] The term "bent" is intended to mean a molecular shape associated with a non-collinear distribution of atoms or groups of atoms around a center of symmetry. Such a shape may arise, for example, due to the presence of lone pairs of electrons or steric effects.
[0048] The term "birefringence" is intended to mean the difference in refractive index in different directions within a polymer film or coating. The term usually refers to the difference between the x-axis or y-axis (in-plane) and z-axis (out-of-plane) refractive indices.
[0049] The term "charge transport", when referring to a layer, material, component, or structure, is intended to mean that such layer, material, component, or structure facilitates the movement of such charge through the thickness of such layer, material, component, or structure with relative efficiency and low charge loss. Hole transport materials facilitate positive charges and electron transport materials facilitate negative charges. Although light-emitting materials may also have some charge transport properties, the term "charge transport layer, material, component, or structure" is not intended to include layers, materials, components, or structures whose primary function is light emission.
[0050] The term "coating" is intended to mean any layer of material applied over a surface. Coating can also mean the process of applying a material to a surface. The term "spin coating" is intended to mean a specific process used to place a uniform thin film on a flat substrate. Generally, in "spin coating", a small amount of coating material is applied to the center of a substrate that is rotating slowly or not at all. The substrate is then rotated at a specific speed to spread the coating material evenly by centrifugal force.
[0051] The term "compound" is intended to mean an uncharged substance composed of molecules further comprising atoms, the atoms of which cannot be separated from their corresponding molecules by physical means without breaking chemical bonds. The term is intended to include oligomers and polymers.
[0052] The term "crosslinkable group" or "crosslinking group" is intended to mean a group on a compound or polymer chain that can be attached to another compound or polymer chain (where the attachment is a covalent bond) by thermal treatment, use of an initiator, or exposure to radiation. In some embodiments, the radiation is ultraviolet or visible radiation. Examples of crosslinkable groups include, but are not limited to, vinyl, acrylate, perfluorovinyl ether, 1-benzo-3,4-cyclobutane, o-quinodimethane groups, siloxane, cyanate groups, cyclic ethers (epoxides), internal alkenes (e.g., stilbene), cycloalkenes, and acetylene groups.
[0053] The term "coefficient of linear thermal expansion (CTE or α)" is intended to mean the parameter that defines the amount a material expands or contracts as a function of temperature. The coefficient of linear thermal expansion is expressed as the change in length per degree Celsius, and is typically expressed in units of μm / m / °C or ppm / °C. α=(ΔL / L0) / ΔT The measured CTE values disclosed herein are generated by known methods during a second heating scan from 50° C. to 250° C. Understanding the relative expansion / contraction properties of materials can be an important consideration in the fabrication and / or reliability of electronic devices.
[0054] The term "dopant" is intended to mean a material that, in a layer containing a host material, changes the electronic properties or the targeted wavelengths of radiation emission, acceptance or filtering of that layer compared to the electronic properties or the wavelengths of radiation emission, acceptance or filtering of a layer in the absence of such material.
[0055] The term "electroactive" as it relates to a layer or material is intended to refer to a layer or material that electronically facilitates the operation of the device. Examples of electroactive materials include, but are not limited to, materials that conduct, inject, transport, or block charge (which can be either electrons or holes), or materials that emit radiation, or materials that exhibit a change in concentration of electron-hole pairs when subjected to radiation. Examples of inactive materials include, but are not limited to, planarizing materials, insulating materials, and environmental barrier materials.
[0056] The term "tensile elongation" or "tensile strain" is intended to mean the percentage increase in length that occurs in a material before it breaks under an applied tensile stress, which can be measured, for example, by ASTM method D882.
[0057] The prefix "fluoro" is intended to indicate that one or more hydrogen atoms in the group have been replaced with fluorine.
[0058] The term "glass transition temperature (T g"Glass transition" is intended to mean the temperature at which an irreversible change occurs within the amorphous domains of an amorphous or semicrystalline polymer when the material suddenly changes from a rigid, glassy, or brittle state to a state that is flexible or elastic. Microscopically, the glass transition occurs when the normally coiled, motionless polymer chains become free to rotate and pass one another. T g can be measured using differential scanning calorimetry (DSC), thermomechanical analysis (TMA) or dynamic mechanical analysis (DMA) or other methods.
[0059] The prefix "hetero" indicates that one or more carbon atoms have been replaced with a different atom. In some embodiments, the heteroatom is O, N, S, or a combination thereof.
[0060] The term "host material" is intended to mean a material to which a dopant is added. The host material may or may not have electronic properties or the ability to emit, receive or filter radiation. In some embodiments, the host material is present in a higher concentration.
[0061] The term "isothermal weight loss" is intended to mean the property of a material that is directly related to its isothermal stability. Isothermal weight loss is typically measured at a constant temperature of interest by differential thermogravimetric analysis (TGA). Materials with high thermal stability generally exhibit a very low percentage of isothermal weight loss at the required use or processing temperature for a desired period of time, and therefore can be used in applications at these temperatures without significant loss of strength, outgassing and / or changes in structure.
[0062] The term "liquid composition" is intended to mean a liquid medium in which a material is dissolved to form a solution, dispersed to form a dispersion, or suspended to form a suspension or emulsion.
[0063] The term "substrate" is intended to mean a base upon which one or more layers are placed, for example, in forming an electronic device. Non-limiting examples include glass, silicon, and others.
[0064] The term "1% TGA weight loss" is intended to mean the temperature at which 1% of the original polymer weight is lost due to decomposition (elimination of absorbed water).
[0065] The term "optical retardation (or R TH "(b)" is intended to mean the difference between the average in-plane refractive index and the out-of-plane refractive index (i.e., birefringence), which is then multiplied by the thickness of the film or coating. Typically, optical retardation is measured for a particular frequency of light and is reported in units of nanometers.
[0066] The terms "organic electronic device" or sometimes "electronic device" are intended herein to mean a device that includes one or more organic semiconductor layers or materials.
[0067] The term "particle content" is intended to mean the number or count of insoluble particles present in a solution. Measurement of particle content can be performed on the solution itself or on product materials (parts, films, etc.) prepared from those films. This property can be evaluated using a variety of optical methods.
[0068] The term "photoactive" refers to a material or layer that emits light when activated by an applied voltage (as in a light emitting diode or chemical cell), emits light after absorbing a photon (as in a downconverting phosphor device), or responds to radiant energy (as in a photodetector or photovoltaic cell) and produces a signal with or without an applied bias voltage.
[0069] The term "polyamic acid solution" refers to a solution of a polymer containing amic acid units capable of intramolecular cyclization to form imide groups.
[0070] The term "polyimide" refers to condensation polymers derived from difunctional carboxylic acid anhydrides and primary diamines. They contain the imide structure -CO-NR-CO- as linear or heterocyclic units along the main chain of the polymer backbone.
[0071] The term "tetravalent" is intended to mean an atom that has four electrons available for covalent chemical bonding and therefore can form four covalent bonds with other atoms.
[0072] The term "satisfactory," when referring to a property or characteristic of a material, is intended to mean that the property or characteristic meets all requirements / demands for the material in use. For example, an isothermal weight loss of less than 1% at 400° C. for 3 hours in nitrogen can be considered a non-limiting example of a "satisfactory" property in the context of the polyimide films disclosed herein.
[0073] The term "soft bake" is intended to mean a process commonly used in electronics manufacturing in which spin-coated materials are heated to drive off solvents and solidify the film. Soft bake is typically performed at temperatures between 90°C and 110°C on a hotplate or in an exhaust oven to prepare the coated layer or film for subsequent thermal processing.
[0074] The term "substrate" refers to a base material that may be either rigid or flexible and may include one or more layers of one or more materials that may include, but are not limited to, glass, polymer, metal, or ceramic materials, or combinations thereof. The substrate may or may not include electronic components, electronic circuits, or conductive members.
[0075] The term "siloxane" refers to the group RSiORSi-, where R is the same or different at each occurrence and is H, D, C1-20 alkyl, deuterated alkyl, fluoroalkyl, aryl, or deuterated aryl. In some embodiments, one or more carbons in the R alkyl group are substituted with Si. A deuterated siloxane group is one in which one or more R groups are deuterated.
[0076] The term "siloxy" refers to the group RSiO-, where R is the same or different at each occurrence and is H, D, C1-20 alkyl, deuterated alkyl, fluoroalkyl, aryl, or deuterated aryl. A deuterated siloxy group is one in which one or more of the R groups is deuterated.
[0077] The term "silyl" refers to the group RSi-, where R is the same or different at each occurrence and is H, D, C1-20 alkyl, deuterated alkyl, fluoroalkyl, aryl, or deuterated aryl. In some embodiments, one or more carbons in the R alkyl group are replaced with Si. A deuterated silyl group is one in which one or more R groups are deuterated.
[0078] The term "laser particle counter testing" refers to a method used to evaluate the particle content of polyamic acid and other polymer solutions whereby a representative sample of the test solution is spin coated onto a 5 inch silicon wafer and soft baked / dried. Films so prepared are evaluated for particle content by any number of standard measurement techniques. Such techniques include laser particle detection and others known in the art.
[0079] The term "tensile modulus" is intended to mean a measure of the stiffness of a solid material that defines the initial relationship between stress (force per unit area) and strain (proportional deformation) in a material such as a film. A commonly used unit is gigapascals (GPa).
[0080] The term "tensile strength" is intended to mean a measure of the maximum stress a material can withstand while being stretched or pulled before breaking. In contrast to "tensile modulus," which measures the amount a material elastically deforms per unit tensile stress applied, the "tensile strength" of a material is the maximum amount of tensile stress it can take before failing. A commonly used unit is megapascals (MPa).
[0081] The term "tensile elongation" is intended to mean the percentage increase in length that occurs in a material before it breaks under an applied tensile stress. It can be measured, for example, by ASTM method D882 and is a unitless quantity.
[0082] The term "tetracarboxylic acid component" is intended to mean a tetravalent moiety attached to the four carboxy groups of a tetracarboxylic acid compound. The tetracarboxylic acid compound may be a tetracarboxylic acid, a tetracarboxylic acid monoanhydride, a tetracarboxylic acid dianhydride, a tetracarboxylic acid monoester, or a tetracarboxylic acid diester. The tetracarboxylic acid component is derived from a tetracarboxylic acid compound. The tetracarboxylic acid component may also be described as being made from a tetracarboxylic acid compound.
[0083] The term "transparent" or "transparency" refers to the physical property of a material that allows light to pass through the material without being scattered. It may also be true that materials that exhibit high transparency exhibit low optical retardation and / or low birefringence. The term "transmittance" refers to the percentage of light of a given wavelength striking the film that passes through the film so that it is present or detectable on the other side. Optical transmittance measurements within the visible range (380 nm to 800 nm) are particularly useful for characterizing the film color characteristics that are most important for understanding the in-use properties of the polyimide films disclosed herein. Furthermore, because radiation of specific wavelengths is often used in the manufacture of films for use in organic electronic devices such as OLEDs, further "transmittance" criteria are specified. For example, after a display is constructed, a laser lift-off process is used to remove the polyimide film from the glass on which it was cast. The laser wavelengths commonly used in this process are 308 nm or 355 nm. Thus, in this context, it is desirable for the polyimide film to have near zero transmittance at these wavelengths. Additionally, during the construction of a display device, several process steps can be accomplished using the process of photolithography, where a photopolymer is exposed through a glass substrate and a polyimide coating. Given that photolithography radiation typically has a wavelength of 365 nm, in this regard, it is desirable for the polyimide film to have at least some transmittance (typically at least 15%) at this wavelength to allow for proper photopolymer exposure.
[0084] The term "yellowness index (or YI)" refers to the magnitude of yellowness compared to a standard. A positive value of YI indicates the presence and magnitude of yellow color. Materials with a negative YI appear bluish. It should also be noted that YI can be solvent dependent, especially for polymerization and / or curing processes at high temperatures. The magnitude of color introduced using DMAC as a solvent may differ from the magnitude of color introduced using, for example, NMP as a solvent. This may occur as a result of the inherent properties of the solvent and / or properties associated with low levels of impurities contained in various solvents. A particular solvent is often preselected to achieve a desired YI value for a particular application.
[0085] In structures in which the bonds of the substituents pass through one or more rings, as shown below:
[0086] [ka]
[0087] It is meant that the substituent R may be attached at any available position on the ring or rings.
[0088] The phrase "adjacent to," when used to refer to layers in a device, does not necessarily mean that one layer is directly next to another layer. On the other hand, the phrase "adjacent R groups" is used to refer to R groups that are adjacent to each other in a chemical formula (i.e., R groups that are on atoms that are linked by a bond). Exemplary adjacent R groups are shown below.
[0089] [ka]
[0090] Unless otherwise expressly stated herein or indicated in connection with use to the contrary, when an embodiment of the subject matter herein is stated or described as comprising, including, containing, having, consisting of, or composed of a particular feature or element, one or more features or elements in addition to those expressly stated or described may be present in the embodiment. An alternative embodiment of the subject matter disclosed herein may be stated as consisting essentially of a particular feature or element, but in that embodiment, no feature or element is present therein that materially alters the principle of operation or distinguishing characteristics of the embodiment. A further alternative embodiment of the subject matter described herein may be stated as consisting of a particular feature or element, but in that embodiment or in an intangible variation thereof, only the feature or element specifically stated or described is present.
[0091] Furthermore, unless expressly stated to the contrary, "or" means an inclusive "or" and not an exclusive "or." For example, condition A or B is satisfied by any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist).
[0092] Additionally, the use of "a" or "an" is used to describe elements and components described herein. This is done merely for convenience and to give a general sense of the scope of the invention. This description should be interpreted to include one or at least one, and the singular also includes the plural unless it is clear that it has a different meaning.
[0093] The group numbers corresponding to the vertical columns of the periodic table of elements are given in CRC Handbook of Chemistry and Physics, 81 st Uses the "New Notation" conventions as seen in Edition (2000-2001).
[0094] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of embodiments of the present invention, suitable methods and materials are described below. All publications, patent applications, patents, and other documents mentioned herein are incorporated by reference in their entirety, unless a specific section is cited. In case of conflict, the present specification, including definitions, will control. Furthermore, the materials, methods, and examples are illustrative only and are not intended to be limiting.
[0095] To the extent not described herein, many of the details regarding specific materials, processing operations and circuitry are conventional and can be found in textbooks and other sources in the art of organic light emitting diode displays, photodetectors, photovoltaics and semiconductor components.
[0096] 2. Polyimide film having a repeating unit structure within formula I A solution containing a polyamic acid in a high boiling aprotic solvent is provided, wherein the polyamic acid comprises one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components is a tetravalent organic group derived from a bent dianhydride or aromatic dianhydride containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, and at least one of the diamine components is a divalent organic group derived from a bent diamine or aromatic diamine containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl, and fluoroalkyl.
[0097] Further provided is a polyimide film produced from a solution containing a polyamic acid in a high boiling aprotic solvent, wherein the polyamic acid comprises one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components being a tetravalent organic group derived from a bent dianhydride or an aromatic dianhydride containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings, and at least one of the diamine components being a divalent organic group derived from a bent diamine or an aromatic diamine containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- bond or a direct chemical bond between aromatic rings; R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl, and fluoroalkyl.
[0098] The tetracarboxylic acid component is prepared from the corresponding dianhydride monomer, where the dianhydride monomer is selected from the group consisting of 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-hexafluoroisopropylidenebisphthalic dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-bisphenol-A dianhydride (BPADA), asymmetric 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), hydroquinone diphthalic anhydride (HQDEA), ethylene glycol bis(trimellitic anhydride) (TMEG-100), bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid) 1,4-phenylene ester (TAHQ or M1225), and the like, and combinations thereof.
[0099] In some embodiments, additional dianhydride monomers are used, non-limiting examples of which include pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and the like, and combinations thereof.
[0100] In some embodiments, monoanhydride monomers are also used as endblocking groups.
[0101] In some embodiments, the monoanhydride monomer is selected from the group consisting of phthalic anhydride and the like and derivatives thereof.
[0102] In some embodiments, the monoanhydride is present in an amount up to 5% of the total tetracarboxylic acid composition.
[0103] The diamine components are 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2'-bis(trifluoromethyl)benzidine (TFMB), 4,4'-methylenedianiline (MDA), 4,4'-[1,3-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-M), 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P), 4,4'-oxydianiline (4,4'-ODA), m-phenylenediamine (MPD), 3,4'-oxydianiline ( 3,4'-ODA), 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 4,4'-diaminodiphenyl sulfide (ASD), 2,2-bis[4-(4-amino-phenoxy)phenyl]sulfone (BAPS), 2,2-bis[4-(3-aminophenoxy)-phenyl]sulfone (m-BAPS), 1,4'-bis(4-aminophenoxy)benzene (TPE-Q), 1,3'-bis(4-aminophenoxy)benzene (TPE-R), 1,3'-bis (4-aminophenoxy)benzene (APB-133), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-diaminobenzanilide (DABA), methylenebis(anthranilic acid) (MBAA), 1,3'-bis(4-aminophenoxy)-2,2-dimethylpropane (DANPG), 1,5-bis(4-aminophenoxy)pentane (DA5MG), 2,2'-bis[4-(4-aminophenoxypenyl)]hexafluoropropane (HFBAPP), 2,2-bis(4-aminophenyl)hexafluoropropane (HFBAPP), The diamine monomers may be selected from the group consisting of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Bis-A-AF), 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Bis-AP-AF), 2,2-bis(3-amino-4-methylphenyl)hexafluoropropane (Bis-AT-AF), 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6BFBAPB), 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane (TMMDA), and the like, and combinations thereof.
[0104] In some embodiments, additional diamine monomers are used, non-limiting examples of which include p-phenylenediamine (PPD), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 3,3'-dimethyl-4,4'-diaminobiphenyl (o-tolidine), 3,3'-dihydroxy-4,4'-diaminobiphenyl (HAB), 9,9'-bis(4-aminophenyl)fluorene (FDA), o-tolidine sulfone (TSN), 2,3,5,6-tetramethyl-1,4-phenylenediamine (TMPD), 2,4-diamino-1,3,5-trimethylbenzene (DAM), 3,3',5,5'-tetramethylbenzidine (3355TMB), 2,2'-bis(trifluoromethyl)benzidine (22TFMB or TFMB), and the like, and combinations thereof.
[0105] In some embodiments, monoamine monomers are also used as endblocking groups.
[0106] In some embodiments, the monoamine monomer is selected from the group consisting of aniline and its derivatives.
[0107] In some embodiments, the monoamine is present in an amount up to 5% of the total amine composition.
[0108] The high boiling polar aprotic solvent is selected from the group consisting of N-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), dimethylformamide (DMF), γ-butyrolactone, dibutyl carbitol, butyl carbitol acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, and the like, and combinations thereof.
[0109] In some embodiments, the polyamic acid contains one tetracarboxylic acid component.
[0110] In some embodiments, the polyamic acid contains two tetracarboxylic acid components.
[0111] In some embodiments, the polyamic acid contains three tetracarboxylic acid components.
[0112] In some embodiments, the polyamic acid contains four or more tetracarboxylic acid components.
[0113] In some embodiments, one of the other tetracarboxylic acid components of the polyamic acid is 4,4'-oxydiphthalic dianhydride (ODPA).
[0114] In some embodiments, one of the tetracarboxylic acid components of the polyamic acid is 4,4'-hexafluoroisopropylidenediphthalic anhydride (6FDA).
[0115] In some embodiments, one or more of the tetracarboxylic acid components of the polyamic acid are tetravalent organic groups derived from bent dianhydrides or aromatic dianhydrides containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- bonds or direct chemical bonds between aromatic rings as disclosed herein.
[0116] In some embodiments, one or more of the tetracarboxylic acid components of the polyamic acid are dianhydrides, which are traditionally considered to be rigid at room temperature as disclosed herein.
[0117] In some embodiments, the polyamic acid contains one tetracarboxylic acid component, where the tetracarboxylic acid component is present at a mole percent of 100%.
[0118] In some embodiments, the polyamic acid contains two tetracarboxylic acid components, with each tetracarboxylic acid component present at a mole percent of 0.1% to 99.9%.
[0119] In some embodiments, the polyamic acid contains three tetracarboxylic acid components, with each tetracarboxylic acid component present at a mole percent of 0.1% to 99.9%.
[0120] In some embodiments, the polyamic acid contains four or more tetracarboxylic acid components, with the tetracarboxylic acid components present at a mole percent of 0.1% to 99.9%.
[0121] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 100% 4,4'-oxydiphthalic anhydride (ODPA).
[0122] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 90% 4,4'-oxydiphthalic anhydride (ODPA) and 10% of one or more other dianhydride compounds disclosed herein.
[0123] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 80% 4,4'-oxydiphthalic anhydride (ODPA) and 20% of one or more other dianhydride compounds disclosed herein.
[0124] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 70% 4,4'-oxydiphthalic anhydride (ODPA) and 30% of one or more other dianhydride compounds disclosed herein.
[0125] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 60% 4,4'-oxydiphthalic anhydride (ODPA) and 40% of one or more other dianhydride compounds disclosed herein.
[0126] In some embodiments, the tetracarboxylic acid component of the polyamic acid is 50% 4,4'-oxydiphthalic anhydride (ODPA) and 50% of one or more other dianhydride compounds disclosed herein.
[0127] In some embodiments, the polyamic acid contains one monomeric diamine component.
[0128] In some embodiments, the polyamic acid contains two monomeric diamine components.
[0129] In some embodiments, the polyamic acid contains three or more monomeric diamine components.
[0130] In some embodiments, the monomeric diamine component of the polyamic acid is 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P).
[0131] In some embodiments, the monomeric diamine component of the polyamic acid is 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0132] In some embodiments, the monomeric diamine component of the polyamic acid is 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0133] In some embodiments, the monomeric diamine component of the polyamic acid is benzene-1,3-diamine (MPD).
[0134] In some embodiments, the monomeric diamine component of the polyamic acid is 3,3'-sulfonyldianiline (DDS).
[0135] In some embodiments, the monomeric diamine component of the polyamic acid is 2,2-bis-[4-(4-aminophenoxyphenyl)]hexafluoropropane (HFBAPP).
[0136] In some embodiments, for one monomeric diamine component of the polyamic acid, the mole percentage of the one monomeric diamine component is 100%.
[0137] In some embodiments, for two monomeric diamine components of a polyamic acid, the mole percentage of each of the two monomeric diamine components is between 0.1% and 99.9%.
[0138] In some embodiments, for the three monomeric diamine components of the polyamic acid, the mole percentage of each of the three monomeric diamine components is between 0.1% and 99.9%.
[0139] In some embodiments, for four or more monomeric diamine components of the polyamic acid, the mole percentage of each of the four or more monomeric diamine components is between 0.1% and 99.9%.
[0140] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 95% 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 5% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0141] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 90% 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline (Bis-P) and 10% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0142] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 80% 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 20% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0143] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 70% 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 30% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0144] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 60% 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 40% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0145] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 50% 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 50% 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0146] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 95% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 5% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0147] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 90% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 10% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0148] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 80% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 20% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0149] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 70% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 30% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0150] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 60% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 40% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0151] In some embodiments, the monomeric diamine component of the polyamic acid is, in mole percent, 50% 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 50% 1,3'-bis(4-amino-phenoxy)benzene (APB-133).
[0152] In some embodiments, the molar ratio of the tetracarboxylic acid component to the diamine component of the polyamic acid is 50 / 50.
[0153] In some embodiments, the solvent in the solution containing the polyamic acid is N-methyl-2-pyrrolidone (NMP).
[0154] In some embodiments, the solvent in the solution containing the polyamic acid is dimethylacetamide (DMAc).
[0155] In some embodiments, the solvent in the solution containing the polyamic acid is dimethylformamide (DMF).
[0156] In some embodiments, the solvent in the solution containing the polyamic acid is gamma-butyrolactone.
[0157] In some embodiments, the solvent in the solution containing the polyamic acid is dibutyl carbitol.
[0158] In some embodiments, the solvent in the solution containing the polyamic acid is butyl carbitol acetate.
[0159] In some embodiments, the solvent in the solution containing the polyamic acid is diethylene glycol monoethyl ether acetate.
[0160] In some embodiments, the solvent in the solution containing the polyamic acid is propylene glycol monoethyl ether acetate.
[0161] In some embodiments, two or more of the high boiling aprotic solvents identified above are used in the solution containing the polyamic acid.
[0162] In some embodiments, an additional co-solvent is used in the solution containing the polyamic acid.
[0163] In some embodiments, the solution containing the polyamic acid is less than 1 wt % polymer in greater than 99 wt % high boiling polar aprotic solvent.
[0164] In some embodiments, the solution containing the polyamic acid is 1-5 wt % polymer in 95-99 wt % high boiling polar aprotic solvent.
[0165] In some embodiments, the solution containing the polyamic acid is 5-10% by weight polymer in 90-95% by weight high boiling polar aprotic solvent.
[0166] In some embodiments, the solution containing the polyamic acid is 10-15 wt % polymer in 85-90 wt % high boiling polar aprotic solvent.
[0167] In some embodiments, the solution containing the polyamic acid is 15-20% by weight polymer in 80-85% by weight high boiling polar aprotic solvent.
[0168] In some embodiments, the solution containing the polyamic acid is 20-25% by weight polymer in 75-80% by weight high boiling polar aprotic solvent.
[0169] In some embodiments, the solution containing the polyamic acid is 25-30% by weight polymer in 70-75% by weight high boiling polar aprotic solvent.
[0170] In some embodiments, the solution containing the polyamic acid is 30-35% by weight polymer in 65-70% by weight high boiling polar aprotic solvent.
[0171] In some embodiments, the solution containing the polyamic acid is 35-40% by weight polymer in 60-65% by weight high boiling polar aprotic solvent.
[0172] In some embodiments, the solution containing the polyamic acid is 40-45% by weight polymer in 55-60% by weight high boiling polar aprotic solvent.
[0173] In some embodiments, the solution containing the polyamic acid is 45-50% by weight polymer in 50-55% by weight high boiling polar aprotic solvent.
[0174] In some embodiments, the solution containing the polyamic acid is 50% by weight polymer in 50% by weight high boiling point polar aprotic solvent.
[0175] In some embodiments, the polyamic acid has a weight average molecular weight (M) of greater than 100,000 based on gel permeation chromatography using polystyrene standards. W ).
[0176] In some embodiments, the polyamic acid has a weight average molecular weight (M) of greater than 150,000 based on gel permeation chromatography using polystyrene standards. W ).
[0177] In some embodiments, the polyamic acid has a molecular weight (M) of greater than 200,000 based on gel permeation chromatography using polystyrene standards. W ).
[0178] In some embodiments, the polyamic acid has a weight average molecular weight (M) of greater than 250,000 based on gel permeation chromatography using polystyrene standards. W ).
[0179] In some embodiments, the polyamic acid has a weight average molecular weight (M) of 200,000 to 300,000 based on gel permeation chromatography using polystyrene standards. W ).
[0180] In some embodiments, the polyamic acid has a weight average molecular weight (M) of greater than 300,000 based on gel permeation chromatography using polystyrene standards. W ).
[0181] Solutions containing the polyamic acids disclosed herein can be prepared using a variety of available methods with respect to the manner in which the components (i.e., monomers and solvents) are introduced to one another. Numerous variations in producing polyamic acid solutions include the following: (a) The diamine and dianhydride components are premixed together and then added portionwise to the solvent while the mixture is being stirred. (b) A method in which the solvent is added to a stirred mixture of the diamine and dianhydride components (as opposed to (a) above). (c) A method in which the diamine is dissolved exclusively in a solvent and the dianhydride is then added to it in a ratio which makes it possible to control the reaction rate. (d) A method in which the dianhydride component is dissolved exclusively in a solvent and the amine component is then added thereto in a ratio which makes it possible to control the reaction rate. (e) A method in which the diamine and dianhydride components are dissolved separately in a solvent and then the solutions are mixed in a reactor. (f) A process in which a polyamic acid containing an excess of an amine component and another polyamic acid containing an excess of a dianhydride component are preformed and then reacted with each other in a reactor in a manner that allows, inter alia, to produce non-random or block copolymers. (g) A specific portion of the amine and dianhydride components are reacted first, followed by the remaining diamine component, or vice versa. (h) A process in which the ingredients are added partially or wholly in any order to any part or all of the solvent, and further in which any or all of the ingredients may be added as a solution in any or all of the solvent. (i) First reacting one of the dianhydride components with one of the diamine components to give a first polyamic acid, then reacting the other dianhydride component with the other amine component to give a second polyamic acid, and then coupling the amic acids by any one of several methods prior to membrane formation.
[0182] Generally speaking, the solution containing polyamic acid can be obtained from any one of the preparation methods disclosed above. Furthermore, in some embodiments, the polyimide films and related materials disclosed herein can be made from other suitable polyimide precursors, such as, for example, poly(amic acid esters), polyisoimides, and polyamic acid salts. Furthermore, if the polyimide is soluble in a suitable coating solvent, the polyimide can be provided as an already imidized polymer dissolved in a suitable coating solvent.
[0183] The solutions containing the polyamic acids disclosed herein can optionally further contain any one of several additives. Such additives can be antioxidants, heat stabilizers, adhesion promoters, coupling agents (e.g., silanes), inorganic fillers, or various toughening agents, so long as they do not significantly affect the desired polyimide properties.
[0184] Additives can be used in forming polyimide films and can be specifically selected to provide important physical attributes to the film. Beneficial properties commonly sought include, but are not limited to, high and / or low modulus, good mechanical elongation, low in-plane coefficient of thermal expansion (CTE), low coefficient of hygroscopic expansion (CHE), high thermal stability, and a particular glass transition temperature (Tg).
[0185] The solution containing the polyamic acid can then be filtered one or more times to reduce particle content. Polyimide films produced from such filtered solutions can exhibit a reduced number of defects, resulting in superior performance in electronic applications as disclosed herein. Evaluation of filtration efficiency can be performed by laser particle counter testing, where a representative sample of the polyamic acid solution is cast onto a 5-inch silicon wafer. After soft baking / drying, the film is evaluated for particle content by any number of laser particle counting techniques on equipment commercially available and known in the art.
[0186] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of less than 40 particles as measured by laser particle counter testing.
[0187] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of less than 30 particles as measured by laser particle counter testing.
[0188] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of less than 20 particles as measured by laser particle counter testing.
[0189] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of less than 10 particles as measured by laser particle counter testing.
[0190] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of between 2 particles and 8 particles as measured by laser particle counter testing.
[0191] In some embodiments, a solution containing polyamic acid is prepared and filtered to produce a particle content of between 4 particles and 6 particles as measured by laser particle counter testing.
[0192] Any of the above-mentioned embodiments of the solution containing polyamic acid can be combined with one or more other embodiments, so long as they are not mutually exclusive. For example, an embodiment in which the tetracarboxylic acid component of the polyamic acid is 4,4'-oxydiphthalic anhydride (ODPA) can be combined with an embodiment in which the solvent used in the solution is N-methyl-2-pyrrolidone (NMP). The same is true for the other non-mutually exclusive embodiments discussed above. Those skilled in the art will understand which embodiments are mutually exclusive and, as a result, will be able to easily determine the combinations of embodiments contemplated by the present application.
[0193] Exemplary preparations of solutions containing polyamic acid are provided in the Examples. All solution compositions may be expressed by notations commonly used in the art. In mole percent: 100% ODPA, 90% Bis-P, and A solution containing 10% TFMB polyamic acid, e.g. ODPA / / Bis-P / TFMB 100 / / / 90 / 10 It can be expressed as:
[0194] The solutions containing the polyamic acids disclosed herein can be used to produce polyimide films, which can be prepared according to the formula I
[0195] [ka]
[0196] (In the formula, R a is a tetravalent organic radical derived from one or more dianhydrides selected from the group consisting of bent dianhydrides and aromatic dianhydrides containing one or more aromatic tetracarboxylic acid moieties containing -O-, -CO-, NHCO-, -S-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between the aromatic rings, and R bis a divalent organic radical derived from one or more diamines selected from the group consisting of benzylidene and aromatic diamines containing -O-, -CO-, -NHCO-, -S-, -SO-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl. and thus having a repeat unit of The in-plane coefficient of thermal expansion (CTE) is less than 50 ppm / ℃ from 50℃ to 250℃. Glass transition temperature (T g ) exceeds 250°C for polyimide films cured at 260°C in air, The 1% TGA weight loss temperature exceeds 350℃. The tensile modulus is 1.5 GPa to 5.0 GPa. The elongation at break exceeds 10%. The optical retardation is less than 20 nm for a 10 μm film, The birefringence at 633 nm is less than 0.007. Haze is less than 1.0%. b * is less than 5, The transmittance at 400 nm is over 45%. The transmittance at 430 nm is over 80%, The transmittance at 450 nm is over 85%. The transmittance at 550 nm is greater than 88%, and The transmittance at 750 nm is greater than 90%.
[0197] Polyimide film R a The tetravalent organic groups are derived from one or more of the dianhydrides disclosed herein for the corresponding polyamic acid-containing solutions.
[0198] Polyimide film R b The divalent organic groups are derived from one or more of the diamines disclosed herein for the corresponding polyamic acid-containing solutions.
[0199] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 200° C. for a polyimide film cured at 260° C. in air. g ).
[0200] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 225° C. for a polyimide film cured at 260° C. in air. g ).
[0201] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 230° C. for a polyimide film cured at 260° C. in air. g ).
[0202] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 240° C. for a polyimide film cured at 260° C. in air. g ).
[0203] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 250° C. for a polyimide film cured at 260° C. in air. g ).
[0204] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 260° C. for a polyimide film cured at 260° C. in air. g ).
[0205] In some embodiments, the polyimide film has a glass transition temperature (T) of greater than 270° C. for a polyimide film cured at 260° C. in air. g ).
[0206] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 100 nm for a 10 μm film.
[0207] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 90 nm for a 10 μm film.
[0208] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 80 nm for a 10 μm film.
[0209] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 70 nm for a 10 μm film.
[0210] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 60 nm for a 10 μm film.
[0211] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 50 nm for a 10 μm film.
[0212] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 40 nm for a 10 μm film.
[0213] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 30 nm for a 10 μm film.
[0214] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 20 nm for a 10 μm film.
[0215] In some embodiments, the polyimide films disclosed herein have an optical retardation at 550 nm that is less than 10 nm for a 10 μm film.
[0216] Any of the above-described embodiments for the polyimide film can be combined with one or more of the other embodiments, so long as they are not mutually exclusive. For example, an embodiment in which the tetracarboxylic acid component of the polyimide film is 4,4'-oxydiphthalic anhydride (ODPA) can be used to increase the glass transition temperature (T g ) is greater than 200° C. The same is true for other non-mutually exclusive embodiments discussed above. Those skilled in the art will understand which embodiments are mutually exclusive and, as a result, will be able to readily determine combinations of embodiments contemplated by this application.
[0217] The examples provide typical preparations of polyimide films. Film compositions can also be expressed by notations commonly used in the art. Expressed in mole percent: 100% ODPA, 90% Bis-P, and A polyimide film with 10% TFMB, e.g. ODPA / / Bis-P / TFMB 100 / / / 90 / 10 It can be expressed as:
[0218] One or more of the tetracarboxylic acid components and one or more of the diamine components disclosed herein may be combined in other ratios in the high boiling aprotic solvents disclosed herein to prepare solutions that can be used to produce polyimide films having different optical, thermal, electronic and other properties other than those already explicitly disclosed.
[0219] The utility of the polyimide films disclosed herein can be tailored to target electronic applications not only through rational selection of the dianhydride and diamine components, but also through careful selection of the imidization reaction conditions. When the components of the polyimide film exhibit a high degree of molecular flexibility, as do certain materials disclosed herein, the associated film properties can be unexpected for the associated compounds. High light transmission, low-color and T gFilms can be made that provide a combination of very low optical retardation, making them suitable for processing and use in display touch panels and other end uses as disclosed herein. As disclosed herein, the further incorporation of rigid comonomers, such as 2,2'-bis(trifluoromethyl)benzidine (TFMB), improves the film's optical transparency, reduces color, and improves T g An increase in the solubility of the polymer may be observed. All of these changes may be advantageous for the end uses disclosed herein.
[0220] A surprising and unexpected advantage of the above compositions is that properties such as low color can be achieved by thermal curing in an ambient air atmosphere. Color is not adversely affected by curing in air as compared to the more traditional approach of curing in nitrogen or other inert atmospheres. This can have a real strategic advantage as it allows for the adoption of more flexible and often less costly manufacturing processes for displays.
[0221] 3. Preparation method of polyimide film Thermal methods and improved thermal methods for preparing polyimide films are provided which generally include the following steps, in order: coating a substrate with a solution containing a polyamic acid, the polyamic acid comprising one or more tetracarboxylic acid components and one or more diamine components, in a high boiling aprotic solvent; soft baking the coated substrate; and treating the soft baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals, whereby the polyimide film exhibits satisfactory properties for use in electronic applications as disclosed herein.
[0222] Generally, polyimide films can be prepared from solutions containing the corresponding polyamic acids by chemical or thermal conversion processes. The polyimide films disclosed herein are prepared by thermal or modified thermal conversion processes as opposed to chemical conversion processes, particularly when used as flexible replacements for glass in electronic devices.
[0223] Such processes may or may not use a conversion chemical (i.e., catalyst) to convert the polyamic acid cast solution to a polyimide. If a conversion chemical is used, the process may be considered a modified thermal conversion process. In both types of thermal conversion processes, only thermal energy is used to heat the film, both to dry the film of solvent and to carry out the imidization reaction. Thermal conversion processes without a conversion catalyst are generally used to prepare the polyimide films disclosed herein.
[0224] The specific process parameters are preselected with the understanding that it is not just the film composition that produces the properties of interest. Rather, both the cure temperature and the temperature ramp profile also play an important role in achieving the most desired properties for the intended uses disclosed herein. The polyamic acid must be imidized at a temperature that is at or above the temperature of any subsequent processing steps (e.g., deposition of inorganic or other layers required to produce a functional display), but below the temperature at which significant thermal decomposition / discoloration of the polyimide occurs. Thus, the imidization temperature used may vary widely depending on the intended use of the resulting film in an electronic device, with higher temperatures generally being suitable for the preparation of polyimides for device substrates, while relatively lower temperatures may be advantageous for touch screen panels, cover films, and other applications disclosed herein. In some embodiments of the imidization process, an inert atmosphere may be preferred, especially when higher processing temperatures are used for imidization. However, in other embodiments, the imidization reaction can be carried out in ambient air. This can provide process advantages, including overall cost and simplicity.
[0225] In some of the polyamic acids / polyimides disclosed herein, a maximum imidization temperature of 260°C is used because subsequent processing steps do not expose the film to temperatures above this maximum imidization temperature. In some embodiments of this process, the maximum temperature of 260°C is maintained for one hour as the final step of the temperature ramp profile. With the appropriate curing temperature and time, a cured polyimide exhibiting thermal, mechanical and optical properties suitable for the intended display application can be produced. The advantage of such a relatively low temperature curing process with a maximum temperature of 260°C is that no inert atmosphere is required. No degradation of the optical properties of the film is observed, as is the case with imidization processes carried out at higher temperatures in the presence of oxygen.
[0226] However, high temperature imidization processes may be appropriate. In some embodiments of the polyamic acid / polyimide disclosed herein, temperatures between 325°C and 375°C are used because subsequent processing temperatures in excess of 350°C are required, for example for device substrate applications. Selecting the correct cure temperature allows for a fully cured polyimide that achieves the best balance of thermal, mechanical and optical properties. Due to this very high temperature, an inert atmosphere is required in these process embodiments. Typically, oxygen levels below 100 ppm must be used. Extremely low oxygen levels allow for the highest cure temperatures without significant degradation and / or discoloration of the polymer.
[0227] The time used for each potential curing step is also an important process consideration for all process embodiments. Generally, the time used for curing at the highest temperature should be kept to a minimum. For a 350° C. cure, for example, the cure time may be up to an hour or so under an inert atmosphere, but at 400° C., this time must be reduced to avoid thermal decomposition. For imidization below 260° C., the cure time may be an hour or more, but in some embodiments, an inert atmosphere may not be necessary. Generally, the higher the temperature, the shorter the time and the lack of oxygen in the atmosphere. Those skilled in the art will recognize the balance required to optimize the properties of the polyimide for a particular end use.
[0228] In some embodiments, the solution containing the polyamic acid is converted into a polyimide film via a thermal conversion process.
[0229] In some embodiments of the thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the resulting film has a soft bake thickness of 10 μm to 20 μm.
[0230] In some embodiments of the thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the resulting film has a soft bake thickness of less than 10 μm.
[0231] In some embodiments of the thermal conversion process, the coated substrate is soft baked on a hotplate in proximity mode, where nitrogen gas is used to hold the spin-coated substrate directly above the hotplate.
[0232] In some embodiments of the thermal conversion process, the coated substrate is soft baked on a hotplate in full contact mode, where the coated substrate is in direct contact with the hotplate surface.
[0233] In some embodiments of the thermal conversion process, the coated substrate is soft baked on a hotplate using a combination of proximity and full contact modes.
[0234] In some embodiments of the thermal conversion process, the coated substrate is soft baked using a hotplate set at 110°C.
[0235] In some embodiments of the thermal conversion process, the coated substrate is soft baked for a total time of less than 10 minutes.
[0236] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured for two preselected time intervals and at two preselected temperatures, the latter of which can be the same or different.
[0237] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at three preselected temperatures for three preselected time intervals, each of which may be the same or different.
[0238] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at four preselected temperatures for four preselected time intervals, each of which may be the same or different.
[0239] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at five preselected temperatures for five preselected time intervals, each of which may be the same or different.
[0240] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured for six preselected time intervals at six preselected temperatures, each of which may be the same or different.
[0241] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at seven preselected temperatures for seven preselected time intervals, each of which may be the same or different.
[0242] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at eight preselected temperatures for eight preselected time intervals, each of which may be the same or different.
[0243] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at nine preselected temperatures for nine preselected time intervals, each of which may be the same or different.
[0244] In some embodiments of the thermal conversion process, the soft-baked coated substrate is subsequently cured at ten preselected temperatures for ten preselected time intervals, each of which may be the same or different.
[0245] In some embodiments of the thermal conversion process, the preselected temperature is greater than 80°C.
[0246] In some embodiments of the thermal conversion process, the preselected temperature is equal to 100°C.
[0247] In some embodiments of the thermal conversion process, the preselected temperature is greater than 100°C.
[0248] In some embodiments of the thermal conversion process, the preselected temperature is equal to 150°C.
[0249] In some embodiments of the thermal conversion process, the preselected temperature is greater than 150°C.
[0250] In some embodiments of the thermal conversion process, the preselected temperature is equal to 200°C.
[0251] In some embodiments of the thermal conversion process, the preselected temperature is greater than 200°C.
[0252] In some embodiments of the thermal conversion process, the preselected temperature is equal to 250°C.
[0253] In some embodiments of the thermal conversion process, the preselected temperature is greater than 250°C.
[0254] In some embodiments of the thermal conversion process, the preselected temperature is 260°C.
[0255] In some embodiments of the thermal conversion process, the preselected temperature does not exceed 260°C.
[0256] In some embodiments of the thermal conversion process, the preselected temperature is greater than 260°C.
[0257] In some embodiments of the thermal conversion process, the preselected temperature is 280°C.
[0258] In some embodiments of the thermal conversion process, the preselected temperature is greater than 280°C.
[0259] In some embodiments of the thermal conversion process, the preselected temperature is equal to 300°C.
[0260] In some embodiments of the thermal conversion process, the preselected temperature is greater than 300°C.
[0261] In some embodiments of the thermal conversion process, the preselected temperature is equal to 350°C.
[0262] In some embodiments of the thermal conversion process, the preselected temperature is greater than 350°C.
[0263] In some embodiments of the thermal conversion process, the preselected temperature is equal to 400°C.
[0264] In some embodiments of the thermal conversion process, the preselected temperature is greater than 400°C.
[0265] In some embodiments of the thermal conversion process, the preselected temperature is equal to 450°C.
[0266] In some embodiments of the thermal conversion process, the preselected temperature is greater than 450°C.
[0267] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is two minutes.
[0268] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is five minutes.
[0269] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 10 minutes.
[0270] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 15 minutes.
[0271] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 20 minutes.
[0272] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 25 minutes.
[0273] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 30 minutes.
[0274] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 35 minutes.
[0275] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 40 minutes.
[0276] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 45 minutes.
[0277] In some thermal conversion processes, one or more of the preselected time intervals is 50 minutes.
[0278] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 55 minutes.
[0279] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is 60 minutes.
[0280] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is greater than 60 minutes.
[0281] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 60 minutes.
[0282] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 90 minutes.
[0283] In some embodiments of the thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 120 minutes.
[0284] In some embodiments of the thermal conversion process, the thermal conversion process is carried out under an inert atmosphere, for example, N2 gas.
[0285] In some embodiments of the thermal conversion process, the thermal conversion process is carried out under ambient atmospheric conditions, i.e., no effort is made to exclude oxygen, water, or other naturally occurring atmospheric constituents from the process.
[0286] In some embodiments of the thermal conversion process, a method for preparing a polyimide film comprises, in order, the steps of: coating a substrate with a solution containing a polyamic acid, the polyamic acid comprising one or more tetracarboxylic acid components and one or more diamine components; soft-baking the coated substrate; and treating the soft-baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals, whereby the polyimide film exhibits satisfactory properties for use in electronic applications as disclosed herein.
[0287] In some embodiments of the thermal conversion process, a method for preparing a polyimide film comprises the steps of: coating a substrate with a solution containing a polyamic acid, the polyamic acid comprising one or more tetracarboxylic acid components and one or more diamine components; soft-baking the coated substrate; and treating the soft-baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals, whereby the polyimide film exhibits satisfactory properties for use in electronic applications as disclosed herein.
[0288] In some embodiments of the thermal conversion process, a method for preparing a polyimide film consists essentially of the following steps, in order: coating a substrate with a solution containing a polyamic acid, the polyamic acid including one or more tetracarboxylic acid components and one or more diamine components; soft-baking the coated substrate; and treating the soft-baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals, whereby the polyimide film exhibits satisfactory properties for use in electronic applications as disclosed herein.
[0289] Typically, the solutions / polyimides disclosed herein are coated / cured onto a supporting glass substrate to facilitate processing through the remainder of the display manufacturing process. At some point in the process, as determined by the display manufacturer, the polyimide coating is removed from the supporting glass substrate by a mechanical or laser lift-off process. These processes separate the polyimide as a film with the display layers fused from the glass, allowing for flexible formats. Often this polyimide film with the deposited layers is then adhered to a thicker, but still flexible, plastic film to provide support for subsequent fabrication of the display.
[0290] Also provided is a modified thermal conversion process in which a conversion catalyst generally effects the imidization reaction at a lower temperature than would be possible in the absence of such conversion catalyst.
[0291] In some embodiments, a solution containing a polyamic acid is converted into a polyimide film by a modified thermal conversion process.
[0292] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains a conversion catalyst.
[0293] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains a conversion catalyst selected from the group consisting of tertiary amines.
[0294] In some embodiments of the modified thermal conversion process, the solution containing polyamic acid further contains a conversion catalyst selected from the group consisting of tributylamine, dimethylethanolamine, isoquinoline, 1,2-dimethylimidazole, N-methylimidazole, 2-methylimidazole, 2-ethyl-4-imidazole, 3,5-dimethylpyridine, 3,4-dimethylpyridine, 2,5-dimethylpyridine, 5-methylbenzimidazole, and the like.
[0295] In some embodiments of the modified thermal conversion process, the conversion catalyst is present at 5% or less by weight of the solution containing the polyamic acid.
[0296] In some embodiments of the modified thermal conversion process, the conversion catalyst is present at 3% or less by weight of the solution containing the polyamic acid.
[0297] In some embodiments of the modified thermal conversion process, the conversion catalyst is present at 1% or less by weight of the solution containing the polyamic acid.
[0298] In some embodiments of the modified thermal conversion process, the conversion catalyst is present at 1% by weight of the solution containing the polyamic acid.
[0299] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains tributylamine as a conversion catalyst.
[0300] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains dimethylethanolamine as a conversion catalyst.
[0301] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains isoquinoline as a conversion catalyst.
[0302] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 1,2-dimethylimidazole as a conversion catalyst.
[0303] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 3,5-dimethylpyridine as a conversion catalyst.
[0304] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 5-methylbenzimidazole as a conversion catalyst.
[0305] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains N-methylimidazole as a conversion catalyst.
[0306] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 2-methylimidazole as a conversion catalyst.
[0307] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 2-ethyl-4-imidazole as a conversion catalyst.
[0308] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 3,4-dimethylpyridine as a conversion catalyst.
[0309] In some embodiments of the modified thermal conversion process, the solution containing the polyamic acid further contains 2,5-dimethylpyridine as a conversion catalyst.
[0310] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is less than 50 μm.
[0311] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is less than 40 μm.
[0312] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is less than 30 μm.
[0313] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is less than 20 μm.
[0314] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the resulting film has a soft bake thickness of 10 μm to 20 μm.
[0315] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the resulting film has a soft bake thickness of 15 μm to 20 μm.
[0316] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is 18 μm.
[0317] In some embodiments of the modified thermal conversion process, a solution containing a polyamic acid is coated onto a substrate such that the soft bake thickness of the resulting film is less than 10 μm.
[0318] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked on a hotplate in proximity mode, where nitrogen gas is used to hold the coated substrate directly above the hotplate.
[0319] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked on a hotplate in full contact mode, where the coated substrate is in direct contact with the hotplate surface.
[0320] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked on a hotplate using a combination of proximity and full contact modes.
[0321] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 80°C.
[0322] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 90°C.
[0323] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 100°C.
[0324] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 110°C.
[0325] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 120°C.
[0326] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 130°C.
[0327] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked using a hotplate set at 140°C.
[0328] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of greater than 10 minutes.
[0329] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of less than 10 minutes.
[0330] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of less than 8 minutes.
[0331] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of less than 6 minutes.
[0332] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of 4 minutes.
[0333] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of less than 4 minutes.
[0334] In some embodiments of the modified thermal conversion process, the coated substrate is soft baked for a total time of less than 2 minutes.
[0335] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured for two preselected time intervals and at two preselected temperatures, the latter of which can be the same or different.
[0336] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at three preselected temperatures for three preselected time intervals, each of which can be the same or different.
[0337] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at four preselected temperatures for four preselected time intervals, each of which can be the same or different.
[0338] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at five preselected temperatures for five preselected time intervals, each of which can be the same or different.
[0339] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at six preselected temperatures for six preselected time intervals, each of which can be the same or different.
[0340] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at seven preselected temperatures for seven preselected time intervals, each of which can be the same or different.
[0341] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at eight preselected temperatures for eight preselected time intervals, each of which can be the same or different.
[0342] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at nine preselected temperatures for nine preselected time intervals, each of which can be the same or different.
[0343] In some embodiments of the modified thermal conversion process, the soft-baked coated substrate is subsequently cured at ten preselected temperatures for ten preselected time intervals, each of which can be the same or different.
[0344] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 80°C.
[0345] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 100°C.
[0346] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 100°C.
[0347] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 150°C.
[0348] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 150°C.
[0349] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 200°C.
[0350] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 200°C.
[0351] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 220°C.
[0352] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 220°C.
[0353] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 230°C.
[0354] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 230°C.
[0355] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 240°C.
[0356] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 240°C.
[0357] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 250°C.
[0358] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 250°C.
[0359] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 260°C.
[0360] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 260°C.
[0361] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 270°C.
[0362] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 270°C.
[0363] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 280°C.
[0364] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 280°C.
[0365] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 290°C.
[0366] In some embodiments of the modified thermal conversion process, the preselected temperature is greater than 290°C.
[0367] In some embodiments of the modified thermal conversion process, the preselected temperature is equal to 300°C.
[0368] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 300°C.
[0369] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 290°C.
[0370] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 280°C.
[0371] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 270°C.
[0372] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 260°C.
[0373] In some embodiments of the modified thermal conversion process, the preselected temperature is less than 250°C.
[0374] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 2 minutes.
[0375] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 5 minutes.
[0376] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 10 minutes.
[0377] In some embodiments of the modified conversion process, one or more of the preselected time intervals is 15 minutes.
[0378] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 20 minutes.
[0379] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 25 minutes.
[0380] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 30 minutes.
[0381] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 35 minutes.
[0382] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 40 minutes.
[0383] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 45 minutes.
[0384] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 50 minutes.
[0385] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 55 minutes.
[0386] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is 60 minutes.
[0387] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is greater than 60 minutes.
[0388] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 60 minutes.
[0389] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 90 minutes.
[0390] In some embodiments of the modified thermal conversion process, one or more of the preselected time intervals is between 2 minutes and 120 minutes.
[0391] 4. Flexible replacement for glass in electronic devices The polyimide films disclosed herein may be suitable for use in several layers in electronic display devices, such as OLED and LCD displays. Non-limiting examples of such layers include device substrates, touch panels, substrates for color filter sheets, cover films, etc. The specific material property requirements for each application are unique and can be addressed by appropriate composition and processing conditions for the polyimide films disclosed herein.
[0392] In some embodiments, a flexible replacement for glass in an electronic device is provided by Formula I
[0393] [ka]
[0394] (In the formula, Ra is a tetravalent organic radical derived from one or more dianhydrides selected from the group consisting of bent dianhydrides and aromatic dianhydrides containing one or more aromatic tetracarboxylic acid moieties containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- chains or direct chemical bonds between the aromatic rings, and R b is a divalent organic radical derived from one or more diamines selected from the group consisting of benzylidene and aromatic diamines containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl. and thereby, The in-plane coefficient of thermal expansion (CTE) is less than 50 ppm / ℃ from 50℃ to 250℃. Glass transition temperature (T g ) exceeds 250°C for polyimide films cured at 260°C in air, The 1% TGA weight loss temperature exceeds 350℃. The tensile modulus is 1.5 GPa to 5.0 GPa. The elongation at break exceeds 10%. The optical retardation is less than 20 nm for a 10 μm film, The birefringence at 633 nm is less than 0.007. Haze is less than 1.0%. b * is less than 5, The transmittance at 400 nm is over 45%. The transmittance at 430 nm is over 80%, The transmittance at 450 nm is over 85%. The transmittance at 550 nm is greater than 88%, and The transmittance at 750 nm is greater than 90%.
[0395] In some embodiments, a flexible replacement for glass in electronic devices is a polyimide film having a repeating unit of Formula I and a composition disclosed herein.
[0396] 5. Electronic Devices Organic electronic devices that may benefit from having one or more layers comprising at least one compound described herein include, but are not limited to, (1) devices that convert electrical energy into radiation (e.g., light-emitting diodes, light-emitting diode displays, lighting devices, luminaires, or diode lasers), (2) devices that detect signals by electronic processes (e.g., photodetectors, photoconductive cells, photoresistors, photoswitches, phototransistors, phototubes, infrared detectors, biosensors), (3) devices that convert radiation into electrical energy (e.g., photovoltaic devices or solar cells), (4) devices that convert light of one wavelength into light of a longer wavelength (e.g., down-converting phosphor devices), and (5) devices that include one or more electronic components that include one or more organic semiconductor layers (e.g., transistors or diodes). Other uses of the compositions according to the present invention include coating materials for memory storage devices, antistatic films, biosensors, electrochemical devices, solid electrolyte capacitors, energy storage devices such as rechargeable batteries, and electromagnetic shielding applications.
[0397] One example of a polyimide film that can act as a flexible replacement for glass as described herein is shown in FIG. 1. The flexible film 100 can have the properties described in the embodiments of the present disclosure. In some embodiments, the polyimide film that can act as a flexible replacement for glass is included in an electronic device. FIG. 2 illustrates an electronic device 200 that is an organic electronic device. The device 200 has a substrate 100, an anode layer 110 and a second electrical contact layer, a cathode layer 130, and a photoactive layer 120 therebetween. Optionally, there can be additional layers. Adjacent to the anode layer can be a hole injection layer (not shown), sometimes referred to as a buffer layer. Adjacent to the hole injection layer can be a hole transport layer (not shown) that includes a hole transport material. Adjacent to the cathode can be an electron transport layer (not shown) that includes an electron transport material. Optionally, the device may employ one or more additional hole injection or hole transport layers (not shown) next to the anode 110 and / or one or more additional electron injection or electron transport layers (not shown) next to the cathode 130. Layers 110-130 are individually and collectively referred to as organic active layers. Additional layers that may or may not be present include color filters, touch panels, and / or cover sheets. One or more of these layers may also be fabricated from the polyimide films disclosed herein in addition to the substrate 100.
[0398] The different layers are discussed further herein with reference to Figure 2. However, the discussion applies to other configurations as well.
[0399] In some embodiments, the different layers have thicknesses in the following ranges: substrate 100, 5 to 100 microns; anode 110, 500 to 5,000 Å, and in some embodiments 1,000 to 2,000 Å; hole injection layer (not shown), 50 to 2,000 Å, and in some embodiments 200 to 1,000 Å; hole transport layer (not shown), 50 to 3,000 Å, and in some embodiments 200 to 2,000 Å; photoactive layer 120, 10 to 2,000 Å, and in some embodiments 100 to 1,000 Å; electron transport layer (not shown), 50 to 2,000 Å, and in some embodiments 100 to 1,000 Å; cathode 130, 200 to 10,000 Å, and in some embodiments 300 to 5,000 Å. The desired ratio of layer thicknesses depends on the exact nature of the materials used.
[0400] In some embodiments, organic electronic devices (OLEDs) include the flexible alternatives to glass disclosed herein.
[0401] In some embodiments, the organic electronic device includes a substrate, an anode, a cathode, and a photoactive layer therebetween, and further includes one or more additional organic active layers. In some embodiments, the additional organic active layer is a hole transport layer. In some embodiments, the additional organic active layer is an electron transport layer. In some embodiments, the additional organic active layer is both a hole transport layer and an electron transport layer.
[0402] The anode 110 is an electrode that is particularly efficient for injecting positive charge carriers. The anode 110 can be made of materials containing, for example, metals, mixed metals, alloys, metal oxides or mixed metal oxides, or it can be a conductive polymer and mixtures thereof. Suitable metals include Group 11 metals, Groups 4, 5 and 6 metals, and Groups 8-10 transition metals. If the anode is light-transmitting, mixed metal oxides of Groups 12, 13 and 14 metals, such as indium tin oxide, are commonly used. The anode can also include organic materials such as polyaniline, as described in “Flexible light-emitting diodes made from soluble conducting polymer,” Nature vol. 357, pp 477 479 (11 June 1992). At least one of the anode and cathode must be at least partially transparent so that the generated light can be observed.
[0403] The optional hole injection layer may include a hole injection material. The term "hole injection layer" or "hole injection material" is intended to mean an electrically conductive or semiconducting material, which may have one or more functions in an organic electronic device, including, but not limited to, planarization of underlying layers, charge transport and / or charge injection properties, scavenging of impurities such as oxygen or metal ions, and other aspects to enhance or improve the performance of an organic electronic device. The hole injection material may be a polymer, oligomer, or small molecule, and may be in the form of a solution, dispersion, suspension, emulsion, colloidal mixture, or other composition.
[0404] The hole injection layer may be formed of a polymeric material, such as polyaniline (PANI) or polyethylenedioxythiophene (PEDOT), which is often doped with a protonic acid. The protonic acid may be, for example, poly(styrenesulfonic acid), poly(2-acrylamido-2-methyl-1-propanesulfonic acid), and the like. The hole injection layer 120 may include charge transfer compounds, such as copper phthalocyanine and tetrathiafulvalene-tetracyanoquinodimethane (TTF-TCNQ), and the like. In some embodiments, the hole injection layer 120 is made from a dispersion of a conductive polymer and a colloid-forming polymeric acid. Such materials are described, for example, in published U.S. Patent Applications 2004-0102577, 2004-0127637, and 2005-0205860.
[0405] Other layers may include hole transport materials. Examples of hole transport materials for the hole transport layer are summarized, for example, in Kirk-Othmer Encyclopedia of Chemical Technology, Fourth Edition, Vol. 18, p. 837860, 1996, by Y. Wang. Both hole transporting small molecules and hole transporting polymers can be used. Commonly used hole transport molecules include, but are not limited to, 4,4',4''-tris(N,N-diphenyl-amino)-triphenylamine (TDATA), 4,4',4''-tris(N-3-methylphenyl-N-phenyl-amino)-triphenylamine (MTDATA), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-[1,1'-biphenyl]-4,4'-diamine (TPD), 4,4'-bis( Carbazol-9-yl)biphenyl (CBP), 1,3-bis(carbazol-9-yl)benzene (mCP), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), N,N'-bis(4-methylphenyl)-N,N'-bis(4-ethylphenyl)-[1,1'-(3,3'-dimethyl)biphenyl]-4,4'-diamine (ETPD), tetrakis(3-methylphenyl)-N,N,N',N' -2,5-phenylenediamine (PDA), α-phenyl-4-N,N-diphenylaminostyrene (TPS), p-(diethylamino)benzaldehyde diphenylhydrazone (DEH), triphenylamine (TPA), bis[4(N,N-diethylamino)-2-methylphenyl](4-methylphenyl)methane (MPMP), 1-phenyl-3-[p-(diethylamino)styryl]-5-[p-(diethylamino)furan [phenyl]pyrazoline (PPR or DEASP), 1,2-trans-bis(9H-carbazol-9-yl)cyclobutane (DCZB), N,N,N',N'-tetrakis(4-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TTB), N,N'-bis(naphthalen-1-yl)-N,N'-bis-(phenyl)benzidine (α-NPB) and porphyrin compounds such as copper phthalocyanine.Commonly used hole transport polymers include, but are not limited to, polyvinylcarbazole, (phenylmethyl)polysilane, poly(dioxythiophene), polyaniline and polypyrrole. It is also possible to obtain hole transport polymers by doping hole transport molecules such as those mentioned above into polymers such as polystyrene and polycarbonate. In some cases, triarylamine polymers are used, particularly triarylamine-fluorene copolymers. In some cases, the polymers and copolymers are crosslinkable. Examples of crosslinkable hole transport polymers can be found, for example, in published U.S. Patent Application Publication No. 2005-0184287 and published PCT Application WO 2005 / 052027. In some embodiments, the hole transport layer is doped with p-type dopants such as tetrafluorotetracyanoquinodimethane and perylene-3,4,9,10-tetracarboxylic-3,4,9,10-dianhydride.
[0406] Depending on the application of the device, photoactive layer 120 can be a light-emitting layer that is activated by an applied voltage (as in a light-emitting diode or light-emitting electrochemical cell), a layer of material that absorbs light and emits light having a longer wavelength (as in a down-converting phosphor device), or a layer of material that responds to radiant energy and produces a signal with or without an applied bias voltage (as in a photodetector or photovoltaic device).
[0407] In some embodiments, the photoactive layer comprises a compound comprising a light-emitting compound having a photoactive material. In some embodiments, the photoactive layer further comprises a host material. Examples of host materials include, but are not limited to, chrysene, phenanthrene, triphenylene, phenanthroline, naphthalene, anthracene, quinoline, isoquinoline, quinoxaline, phenylpyridine, carbazole, indolocarbazole, furan, benzofuran, dibenzofuran, benzodifuran, and metal quinolinate complexes. In some embodiments, the host material is deuterated.
[0408] In some embodiments, the photoactive layer comprises (a) a dopant capable of electroluminescence having an emission maximum between 380 and 750 nm, (b) a first host compound, and (c) a second host compound. Suitable second host compounds are described above.
[0409] In some embodiments, the photoactive layer comprises only (a) a dopant capable of electroluminescence having an emission maximum between 380 and 750 nm, (b) a first host compound, and (c) a second host compound, wherein no additional materials are present that would substantially alter the principle of operation or distinguishing properties of the layer.
[0410] In some embodiments, the first host is present in a greater concentration, on a weight basis, than the second host in the photoactive layer.
[0411] In some embodiments, the weight ratio of the first host to the second host in the photoactive layer is in the range of 10:1 to 1:10. In some embodiments, the weight ratio is in the range of 6:1 to 1:6, in some embodiments, in the range of 5:1 to 1:2, and in some embodiments, in the range of 3:1 to 1:1.
[0412] In some embodiments, the weight ratio of dopant to total host is in the range of 1:99 to 20:80, and in some embodiments, in the range of 5:95 to 15:85.
[0413] In some embodiments, the photoactive layer includes (a) a red-emitting dopant, (b) a first host compound, and (c) a second host compound.
[0414] In some embodiments, the photoactive layer includes (a) a green-emitting dopant, (b) a first host compound, and (c) a second host compound.
[0415] In some embodiments, the photoactive layer includes (a) a yellow-emitting dopant, (b) a first host compound, and (c) a second host compound.
[0416] The optional layer can function to facilitate electron transport and also serve as a confinement layer to prevent exciton quenching at layer interfaces. Preferably, this layer promotes electron mobility and reduces exciton quenching.
[0417] In some embodiments, such layers include other electron transporting materials. Examples of electron transporting materials that can be used in the optional electron transporting layer include metal chelated oxinoid compounds including metal quinolate derivatives such as tris(8-hydroxyquinolato)aluminum (AlQ), bis(2-methyl-8-quinolinolato)(p-phenylphenolato)aluminum (BAlq), tetrakis-(8-hydroxyquinolato)hafnium (HfQ) and tetrakis-(8-hydroxyquinolato)zirconium (ZrQ), and 2-(4-biphenylyl)-5-(4-t-butylphenyl)-1,3,4-oxadiazole (PB D), azole compounds such as 3-(4-biphenylyl)-4-phenyl-5-(4-t-butylphenyl)-1,2,4-triazole (TAZ) and 1,3,5-tri(phenyl-2-benzimidazole)benzene (TPBI), quinoxaline derivatives such as 2,3-bis(4-fluorophenyl)quinoxaline, phenanthrolines such as 4,7-diphenyl-1,10-phenanthroline (DPA) and 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (DDPA), triazines, fullerenes, and mixtures thereof. In some embodiments, the electron transport material is selected from the group consisting of metal quinolates and phenanthroline derivatives. In some embodiments, the electron transport layer further comprises an n-dopant. N-dopant materials are well known. N-dopants include, but are not limited to, Group 1 and 2 metals, Group 1 and 2 metal salts such as LiF, CsF and Cs2CO3, Group 1 and 2 metal organic compounds such as Li quinolate and molecular n-dopants such as leuco dyes, metal complexes such as W2(hpp)4 (where hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido-[1,2-a]-pyrimidine) and cobaltocene, tetrathianaphthacene, bis(ethylenedithio)tetrathiafulvalene, heterocyclic radicals or diradicals and dimers, oligomers, polymers, dispiro compounds and polycycles of heterocyclic radicals or diradicals.
[0418] An optional electron injection layer may be deposited over the electron transport layer. Examples of electron injection materials include, but are not limited to, Li-containing organometallic compounds, LiF, Li2O, Li quinolate, Cs-containing organometallic compounds, CsF, Cs2O, and Cs2CO3. This layer may react with the underlying electron transport layer, the overlying cathode, or both. If an electron injection layer is present, the amount of material deposited is generally in the range of 1-100 Å, and in some embodiments, 1-10 Å.
[0419] The cathode 130 is an electrode that is particularly efficient for injecting electrons or negative charge carriers. The cathode can be any metal or nonmetal with a lower work function than the anode. Materials for the cathode can be selected from the Group 1 alkali metals (e.g., Li, Cs), the Group 2 (alkaline earth) metals, the rare earth elements, and the Group 12 metals, including the lanthanides and actinides. Materials such as aluminum, indium, calcium, barium, samarium, and magnesium, as well as combinations, can be used.
[0420] It is known to have other layers in organic electronic devices. For example, a layer (not shown) for controlling the amount of positive charge injected and / or for providing band gap matching of the layers or for acting as a protective layer may be present between the anode 110 and the hole injection layer (not shown). Layers known in the art such as copper phthalocyanine, silicon oxynitride, fluorocarbons, silanes, or ultra-thin layers of metals such as Pt can be used. Alternatively, some or all of the anode layer 110, active layer 120, or cathode layer 130 can be surface treated to increase charge carrier transport efficiency. The choice of material for each of the constituent layers is preferably determined by balancing the positive and negative charges in the emitter layer to provide a device with high electroluminescence efficiency.
[0421] It is understood that each functional layer may be composed of two or more layers.
[0422] The device layers can generally be formed by any deposition technique or combination of techniques, including vapor deposition, liquid deposition, and thermal transfer. Substrates such as glass, plastic, and metal can be used. Conventional deposition techniques such as thermal evaporation, chemical vapor deposition, etc. can be used. Organic layers can be applied from solutions or dispersions in suitable solvents using conventional coating or printing techniques, including, but not limited to, spin coating, dip coating, roll-to-roll techniques, inkjet printing, continuous nozzle printing, screen printing, gravure printing, etc.
[0423] For liquid deposition methods, a suitable solvent for a particular compound or related class of compounds can be readily determined by one of ordinary skill in the art. For some applications, it is desirable for the compound to be dissolved in a non-aqueous solvent. Such non-aqueous solvents include those listed in the C1-C 20 They can be relatively polar, such as alcohols, ethers and acid esters, or C1-C 12 The solvent may be relatively non-polar, such as an alkane or an aromatic compound, for example, toluene, xylene, trifluorotoluene, etc. Other suitable liquids for use in preparing liquid compositions containing the novel compounds, either as solutions or dispersions as described herein, include, but are not limited to, chlorinated hydrocarbons (such as methylene chloride, chloroform, chlorobenzene, etc.), aromatic hydrocarbons (such as substituted and unsubstituted toluene and xylene, trifluorotoluene, etc.), polar solvents (such as tetrahydrofuran (THP), N-methylpyrrolidone, etc.), esters (such as ethyl acetate), alcohols (isopropanol), ketones (cyclopentatone), and mixtures thereof. Suitable solvents for electroluminescent materials are described, for example, in published PCT application WO 2007 / 145979.
[0424] In some embodiments, the device is fabricated by liquid deposition of the hole injection layer, the hole transport layer, and the photoactive layer, and by vapor deposition of the anode, the electron transport layer, the electron injection layer, and the cathode onto a flexible substrate.
[0425] It is understood that the efficiency of the device can be improved by optimizing other layers in the device. For example, more efficient cathodes such as Ca, Ba or LiF can be used. Shaped substrates and novel hole transport materials that result in lower operating voltages or increase quantum efficiency can also be applied. Additional layers can also be added to adjust the energy levels of the various layers and promote electroluminescence.
[0426] In some embodiments, the device has the following structure, in order: substrate, anode, hole injection layer, hole transport layer, photoactive layer, electron transport layer, electron injection layer, cathode.
[0427] Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, suitable methods and materials are described below. Furthermore, the materials, methods, and examples are illustrative only and not intended to be limiting. All publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety. EXAMPLES
[0428] The concepts described herein are further illustrated in the following examples, which are not intended to limit the scope of the invention described in the claims.
[0429] The specific film properties will depend on the composition and imidization process used in each case.
[0430] In some embodiments, the polyimide films disclosed herein have a T of greater than 250° C. for films cured at 260° C. in air. g has.
[0431] In some embodiments, the polyimide film has an in-plane coefficient of thermal expansion (CTE) of less than 70 ppm / °C from 50°C to 250°C.
[0432] In some embodiments, the polyimide films disclosed herein have an optical retardation measured at 550 nm that is less than about 20 nm for a 10 μm film.
[0433] In some embodiments, the polyimide films disclosed herein have a b * has.
[0434] A typical sample composition is as follows:
[0435] [Table 1]
[0436] Example A - Preparation of polyamic acid copolymer of ODPA / TFMB / APB-133 (100 / / 80 / 20) with DMAC A 1 liter reaction flask equipped with nitrogen inlet and outlet, mechanical stirrer, and thermocouple was charged with 24.72 g of trifluoromethylbenzidine (TFMB) and 200 g of dimethylacetamide (DMAC). The mixture was stirred at room temperature under nitrogen for approximately 30 minutes to dissolve the TFMB. 5.64 g of 1,3,3-aminophenoxybenzene (APB-133) was then added along with 50 g of DMAC. After the diamine was dissolved, 29.64 g of oxydiphthalic anhydride (ODPA) was added to the reaction with stirring along with 90 g of DMAC. The rate of dianhydride addition was controlled to maintain a maximum reaction temperature below 40°C. The dianhydride was allowed to dissolve and react, and the polyamic acid (PAA) solution was stirred for approximately 24 hours. ODPA was then added in 0.10 g increments to increase the molecular weight of the polymer and the viscosity of the polymer solution in a controlled manner. A Brookfield cone and plate viscometer was used to monitor the solution viscosity by removing a small sample from the reaction flask for testing. A total of 0.20 g of ODPA was added.
[0437] The reaction proceeded for an additional 72 hours under gentle stirring at room temperature to allow for polymer equilibration. The final viscosity of the polymer solution was 10,467 cps at 25° C. The contents of the flask were poured into a 1 liter HDPE bottle, tightly capped, and stored in the refrigerator for future use.
[0438] Example 1 - Spin-coating and imidization of a polyamic acid solution onto a polyimide coating. A portion of the polyamic acid solution from Example A was pressure filtered through a Whatman PolyCap HD 0.45 μm absolute filter into an EFD Nordsen dispensing syringe barrel. The syringe barrel was attached to an EFD Nordsen dispensing apparatus and a few mL of the polymer solution was applied to a 6 inch silicon wafer and spin coated. The spin speed was varied to obtain the desired soft bake thickness of approximately 18 μm. A soft bake was achieved after coating by placing the coated wafer on a hotplate set at 110° C. and first in proximity mode (nitrogen flow to hold the wafer very slightly away from the surface of the hotplate) for 1 minute, followed by direct contact with the hotplate surface for 3 minutes. The thickness of the soft baked film was measured in a Tencor profilometer by removing an area of coating from the wafer and then measuring the difference between the coated and uncoated areas of the wafer. The spin coating conditions were varied as necessary to obtain the desired uniform coating of approximately 15 μm across the entire wafer surface.
[0439] After that, spin-coating conditions were determined, several wafers were coated and soft-baked, and then these coated wafers were placed in a convection oven. After closing the oven door, the oven was ramped to 100°C at 2.5°C / min and held for about 30 minutes, then the temperature was ramped to 260°C at 4°C / min and held for 60 minutes. The curing profile was carried out under air atmosphere. After that, the heating was stopped and the temperature was allowed to slowly return to ambient temperature (no external cooling). The wafer was then removed from the oven and the coating was removed from the wafer by scratching the coating with a knife around the edge of the wafer and then immersing the wafer in water for at least several hours to remove the coating from the wafer. The resulting polyimide film was dried and then subjected to various property measurements. The polyimide film was subjected to various property measurements by using the b * and optical retardation of 35 nm.
[0440] Further synthesis and comparative examples Example B - Preparation of polyamic acid copolymer of ODPA / / Bis-P / TFMB 100 / / 90 / 10 in NMP. This solution containing polyamic acid ODPA / / Bis-P / TFMB 100 / / 90 / 10 was prepared in NMP in a manner similar to that done in Example A above, except for the specific dianhydride and diamine, the relative amounts of each of which were appropriate for this target composition. The prepared solution was poured into 2 liter HDPE bottles, tightly capped, and stored in the refrigerator for later use.
[0441] Example 2 - Spin coating and imidization of polyamic acid solution onto ODPA / / Bis-P / TFMB 100 / / 90 / 10 polyimide coating under ambient atmospheric conditions. The solution containing the polyamic acid copolymer prepared in Example B was filtered, coated onto a 6-inch silicon wafer, soft-baked, and imidized in a manner similar to that described above in Example 1. The imidization temperature profile had a maximum cure temperature of 260° C., and the process was carried out under ambient atmospheric conditions. Heating was then stopped, and the temperature was allowed to slowly return to ambient temperature (no external cooling). The wafer was then removed from the oven, and the coating was removed from the wafer by scratching the coating from around the edge of the wafer with a knife, and then immersing the wafer in water for at least several hours to remove the coating from the wafer. The resulting polyimide film was dried and then subjected to various property measurements. For example, b along with % transmittance (%T) over wavelengths in the range of 350 nm to 780 nm was measured using a Hunter Lab spectrophotometer. * and Yellowness Index were measured. Optical birefringence is measured with a Metricon instrument equipped with a 543 nm laser. Optical retardation is measured using an Axoscan instrument at 550 nm. Thermal measurements of the films were performed using a combination of thermogravimetric and thermomechanical analysis appropriate for the specific parameters reported herein. Mechanical properties were measured using Instron equipment. The property measurements of this film are shown in Table 1.
[0442] Example 3 - Spin coating and imidization of polyamic acid solution onto ODPA / / Bis-P / TFMB 100 / / 90 / 10 polyimide coating in inert atmosphere. The solution containing the polyamic acid copolymer prepared in Example B was filtered, coated onto a 6-inch silicon wafer, soft-baked, and imidized in a manner similar to that described above in Example 1. The maximum cure temperature of the imidization temperature profile was 260° C., and the process was carried out in a nitrogen gas atmosphere. Heating was then stopped, and the temperature was allowed to slowly return to ambient temperature (no external cooling). The wafer was then removed from the oven, and the coating was removed from the wafer by scratching the coating from around the edge of the wafer with a knife, and then immersing the wafer in water for at least several hours to remove the coating from the wafer. The resulting polyimide film was dried and then subjected to various property measurements. For example, the b along with the % transmittance (%T) over wavelengths in the range of 350 nm to 780 nm was measured using a Hunter Lab spectrophotometer. * and Yellowness Index were measured. Optical birefringence is measured with a Metricon instrument equipped with a 543 nm laser. Optical retardation is measured using an Axoscan instrument at 550 nm. Thermal measurements of the films were performed using a combination of thermogravimetric and thermomechanical analysis appropriate for the specific parameters reported herein. Mechanical properties were measured using Instron instruments. The property measurements of this film are shown in Table 1.
[0443] [Table 2]
[0444] It is noted that the thermal, mechanical and optical properties all compare favorably to films imidized in air and nitrogen. Importantly, the color properties of films prepared under ambient atmosphere can be superior to those of N2 in many of the applications disclosed herein. Both films have an R of less than 20 nm at 550 nm. TH has.
[0445] Examples C, D, E, F, G, H and Comparative Example A - Preparation of Polyamic Acid Copolymers in NMP with Composition: Example C: ODPA / / 3,3'DDS 100 / / 100 Example D: ODPA / / Bis-P 100 / / 100 Example E: ODPA / / Bis-P / MPD 100 / / 90 / 10 Example F: ODPA / 6FDA / / Bis-P 90 / 10 / / 100 Example G: ODPA / 6FDA / / Bis-P / TFMB 90 / 10 / / 90 / 10 Example H: ODPA / a-BPDA / / Bis-P / TFMB 60 / 40 / / 90 / 10 Comparative example A: BPDA / / Bis-P 100 / / 100
[0446] Solutions containing polyamic acids of the above compositions were prepared in NMP using similar processes as disclosed for Examples A and B above, except for the specific dianhydrides and diamines, the relative amounts of each of which were appropriate for these target compositions. The prepared solutions were poured into 2 liter HDPE bottles, tightly capped, and stored in the refrigerator for later use.
[0447] Examples 4, 5, 6, 7, 8, 9 and Comparative Example 1 - Spin-coating and imidization of polyamic acid solutions with compositions: Example 4: ODPA / / 3,3'DDS 100 / / 100 Example 5: ODPA / / Bis-P 100 / / 100 Example 6: ODPA / / Bis-P / MPD 100 / / 90 / 10 Example 7: ODPA / 6FDA / / Bis-P 90 / 10 / / 100 Example 8: ODPA / 6FDA / / Bis-P / TFMB 90 / 10 / / 90 / 10 Example 9: ODPA / a-BPDA / / Bis-P / TFMB 60 / 40 / / 90 / 10 Comparative example 1: BPDA / / Bis-P 100 / / 100
[0448] The solutions containing polyamic acid copolymers prepared in Examples C-H and Comparative Example A were filtered, coated onto 6-inch silicon wafers, soft-baked, and imidized in a similar manner as described above in Examples 1-3. The maximum cure temperature of the imidization temperature profile in all cases was 260° C., and the process was carried out under ambient atmospheric conditions or nitrogen gas atmosphere (see Tables 2a and 2b). The heating was then stopped and the temperature was slowly allowed to return to ambient temperature (no external cooling). The wafers were then removed from the oven, and the coating was removed from the wafers by scratching the coating from around the wafer's edge with a knife, and then immersing the wafers in water for at least several hours to remove the coating from the wafers. The resulting polyimide films were dried and then subjected to various property measurements. For example, the b along with the % transmittance (%T) over wavelengths in the range of 350 nm to 780 nm was measured using a Hunter Lab spectrophotometer. * and Yellowness Index were measured. Optical birefringence is measured with a Metricon instrument equipped with a 543 nm laser. Optical retardation is measured using an Axoscan instrument at 550 nm. Thermal measurements of the films were performed using a combination of thermogravimetric and thermomechanical analysis appropriate for the specific parameters reported herein. Mechanical properties were measured using Instron instruments. The property measurements of these films are shown in Tables 2a and 2b.
[0449] [Table 3]
[0450] [Table 4]
[0451] Films of the compositions disclosed herein exhibit low R TH The dianhydride component of Comparative Example 1 is found to have a Tg of over 250° C. combined with a T of 0.01 to 0.05 μm. The dianhydride component of Comparative Example 1 is relatively stiff, and the related polyimide has a significantly higher R TH Shows.
[0452] Examples I-R - Preparation of Polyamic Acid Copolymers in NMP with Composition: Example I: ODPA / / 3,3'DDS / TFMB 100 / / 80 / 20 Example J: ODPA / / Bis-M / TFMB 100 / / 50 / 50 Example K: ODPA / / / TFMB / Bis-P / APB-133 100 / / 50 / 45 / 5 Example L: ODPA / / Bis-P / TFMB / APB-133 100 / / 60 / 30 / 10 Example M: ODPA / 6FDA / / Bis-P / TFMB / APB-133 90 / 10 / / 60 / 30 / 10 Example N: ODPA / M1225 / / Bis-P / TFMB / APB-133 90 / 10 / / 50 / 40 / 10 Example O: ODPA / M1225 / / Bis-P / TFMP 50 / 50 / / 90 / 10 Example P: ODPA / / TFMB / APB-133 100 / / 90 / 10 Example Q: ODPA / / TFMB 100 / / 100 Example R: ODPA / / TFMB / Bis-P 100 / / 80 / 20
[0453] Solutions containing polyamic acids of the above compositions were prepared in NMP using similar processes as disclosed for Examples A and B above, except for the specific dianhydrides and diamines, the relative amounts of each of which were appropriate for these target compositions. The prepared solutions were poured into 2 liter HDPE bottles, tightly capped, and stored in the refrigerator for later use.
[0454] Examples 10-19 - Spin-coating and imidization of polyamic acid solutions with compositions: Example 10: ODPA / / 3,3'DDS / TFMB 100 / / 80 / 20 Example 11: ODPA / / Bis-M / TFMB 100 / / 50 / 50 Example 12: ODPA / / / TFMB / Bis-P / APB-133 100 / / 50 / 45 / 5 Example 13: ODPA / / Bis-P / TFMB / APB-133 100 / / 60 / 30 / 10 Example 14: ODPA / 6FDA / / Bis-P / TFMB / APB-133 90 / 10 / / 60 / 30 / 10 Example 15: ODPA / M1225 / / Bis-P / TFMB / APB-133 90 / 10 / / 50 / 40 / 10 Example 16: ODPA / M1225 / / Bis-P / TFMP 50 / 50 / / 90 / 10 Example 17: ODPA / / TFMB / APB-133 100 / / 90 / 10 Example 18: ODPA / / TFMB 100 / / 100 Example 19: ODPA / / TFMB / Bis-P 100 / / 80 / 20
[0455] The solutions containing polyamic acid copolymers prepared in Examples I-R were filtered, coated onto 6-inch silicon wafers, soft-baked, and imidized in a similar manner as described above in Examples 1-3 and 4-9. The cure temperature of the imidization temperature profile in all cases did not exceed 260°C, and the process was carried out under ambient air conditions or nitrogen gas atmosphere (see Tables 3a, 3b, and 3c). Heating was then stopped and the temperature was slowly allowed to return to ambient temperature (no external cooling). The wafers were then removed from the oven and the coating was removed from the wafers by scratching the coating from around the wafer edge with a knife, and then immersing the wafers in water for at least several hours to remove the coating from the wafers. The resulting polyimide films were dried and then subjected to various property measurements. For example, the b along with the % transmittance (%T) over wavelengths in the range of 350 nm to 780 nm was measured using a Hunter Lab spectrophotometer. *and Yellowness Index were measured. Optical birefringence is measured with a Metricon instrument equipped with a 543 nm laser. Optical retardation is measured using an Axoscan instrument at 550 nm. Thermal measurements of the films were performed using a combination of thermogravimetric and thermomechanical analysis appropriate for the specific parameters reported herein. Mechanical properties were measured using Instron instruments. The property measurements of these films are shown in Tables 3a, 3b, and 3c.
[0456] [Table 5]
[0457] [Table 6]
[0458] [Table 7]
[0459] It should be noted that not all of the operations described above in the general description or in the examples are required, some of the specific operations may not be required, and one or more additional operations may be performed in addition to the operations described. Furthermore, the order in which the operations are listed is not necessarily the order in which the operations are performed.
[0460] In the above specification, the present concepts have been described with reference to specific embodiments. However, those skilled in the art will appreciate that various modifications and changes can be made without departing from the scope of the invention as set forth in the following claims. Accordingly, the specification and figures are to be regarded in an illustrative rather than a restrictive sense, and all such modifications are intended to be included within the scope of the present invention.
[0461] Benefits, other advantages, and solutions to problems have been described above with respect to particular embodiments. However, the benefits, advantages, and solutions to problems, as well as any features that may give rise to or enhance any benefit, advantage, or solution, are not to be construed as critical, required, or essential features of any or all claims.
[0462] For clarity, it should be understood that certain features are described herein in the context of separate embodiments and may also be provided in combination in a single embodiment. Conversely, for brevity, various features described in the context of a single embodiment may also be provided individually or in any subcombination. The use of various ranges of numerical values specified herein is described as approximations, as if the minimum and maximum values within the stated ranges were both preceded by the word "about". In this manner, slight variations above and below the stated ranges may be used to achieve substantially the same results as the numerical values within the ranges. Also, the disclosure of these ranges is intended to be a continuous range including every value between the minimum and maximum average values, including fractional values that may result when a portion of a component of one value is mixed with a portion of a component of a different value. Furthermore, when broader and narrower ranges are disclosed, it is within the contemplation of the present invention to match the minimum value from one range with the maximum value from another range, and vice versa. The present invention includes the following embodiments. 1. A solution composition comprising a polyamic acid in a high-boiling aprotic solvent, The polyamic acid includes one or more tetracarboxylic acid components and one or more diamine components, at least one of the tetracarboxylic acid components is a tetravalent organic group derived from a bent dianhydride or aromatic dianhydride containing an -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- bond or a direct chemical bond between aromatic rings; at least one of the diamine components is a divalent organic group derived from a benzodiamine or aromatic diamine that contains an -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- bond or a direct chemical bond between aromatic rings; R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl, and fluoroalkyl. 2. The solution composition according to claim 1, wherein the tetracarboxylic acid component is derived from a dianhydride selected from the group consisting of 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-hexafluoroisopropylidenebisphthalic dianhydride (6FDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride (DSDA), 4,4'-bisphenol-A dianhydride (BPADA), asymmetric 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA), hydroquinone diphthalic anhydride (HQDEA), ethylene glycol bis(trimellitic anhydride) (TMEG-100), bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid) 1,4-phenylene ester (TAHQ or M1225), and the like, and combinations thereof. 3. The diamine component is 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2'-bis(trifluoromethyl)benzidine (TFMB), 4,4'-methylenedianiline (MDA), 4,4'-[1,3-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-M), 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P), 4,4'-oxydianiline (4,4'-ODA), m-phenylenediamine (MPD), 3 ... 3,4'-ODA, 3,3'-diaminodiphenyl sulfone (3,3'-DDS), 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 4,4'-diaminodiphenyl sulfide (ASD), 2,2-bis[4-(4-amino-phenoxy)phenyl]sulfone (BAPS), 2,2-bis[4-(3-aminophenoxy)-phenyl]sulfone (m-BAPS), 1,4'-bis(4-aminophenoxy)benzene (TPE-Q), 1,3'-bis(4-aminophenoxy)benzene (TPE-R), 1,3'-bis( 4-aminophenoxy)benzene (APB-133), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-diaminobenzanilide (DABA), methylenebis(anthranilic acid) (MBAA), 1,3'-bis(4-aminophenoxy)-2,2-dimethylpropane (DANPG), 1,5-bis(4-aminophenoxy)pentane (DA5MG), 2,2'-bis[4-(4-aminophenoxypenyl)]hexafluoropropane (HFBAPP), 2,2-bis(4-aminophenyl)hexafluoropropane The solution composition according to claim 2, which is derived from a diamine selected from the group consisting of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (Bis-AP-AF), 2,2-bis(3-amino-4-methylphenyl)hexafluoropropane (Bis-AT-AF), 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6BFBAPB), 3,3'5,5'-tetramethyl-4,4'-diaminodiphenylmethane (TMMDA), and the like, and combinations thereof. 4. The solution composition according to claim 3, further comprising one or more additional tetracarboxylic acid components. 5. The solution composition according to 3 or 4 above, further comprising one or more additional diamine components. 6. The solution composition according to 3 above, wherein the tetracarboxylic acid component of the polyamic acid is 4,4'-oxydiphthalic dianhydride (ODPA). 7. The solution composition according to claim 6, wherein the diamine component of the polyamic acid is selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P). 8. The solution composition according to claim 6, wherein the diamine component of the polyamic acid is selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine (TFMB) and 1,3'-bis(4-amino-phenoxy)benzene (APB-133). 9. A polyimide film prepared from the solution composition according to 7 or 8 above. 10. Formula I [ka] (In the formula, R a is a tetravalent organic radical derived from one or more dianhydrides selected from the group consisting of bent dianhydrides and aromatic dianhydrides containing one or more aromatic tetracarboxylic acid moieties containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O-, or -CR2- chains or direct chemical bonds between the aromatic rings, and R b is a divalent organic radical derived from one or more diamines selected from the group consisting of benzylidene and aromatic diamines containing -O-, -CO-, -NHCO-, -S-, -SO2-, -CO-O- or -CR2- chains or direct chemical bonds between aromatic rings, R is the same or different at each occurrence and is selected from the group consisting of H, F, alkyl and fluoroalkyl. A polyimide film comprising the repeating unit: 11. In-plane coefficient of thermal expansion (CTE) less than 75 ppm / ℃ from 50℃ to 250℃; The glass transition temperature (T) of polyimide film cured at 260°C in air was greater than 250°C. g ), 1% TGA weight loss temperature above 450℃, Tensile modulus between 1.5GPa and 5.0GPa; Elongation at break of more than 20% Optical retardation at 550 nm, which is less than 100 nm for a 10 μm film; Birefringence at 633 nm that is less than 0.002; Haze less than 1.0%; b is less than 3 * , A yellowness index of less than 5; and Over 88% average transmittance from 380nm to 780nm 11. The polyimide film according to claim 10, 12. The polyimide film according to claim 11, exhibiting an optical retardation at 550 nm that is less than 20 nm for a 10 μm film. 13. A method for preparing a polyimide film, selected from the group consisting of a thermal method and an improved thermal method, said thermal method comprising the steps of: Coating a substrate with the solution described in 1; soft baking the coated substrate; treating the soft-baked coated substrate at a plurality of preselected temperatures for a plurality of preselected time intervals. The method includes, in order: 14. The method of claim 13, wherein the preselected maximum temperature is 320°C. 15. The method of claim 13, wherein the preselected maximum temperature is 260°C. 16. The method according to claim 13, wherein the method is carried out under ambient atmospheric conditions. 17. A flexible replacement for glass in an electronic device, comprising the polyimide film of claim 10. 18. An electronic device comprising the flexible substitute for glass according to claim 17. 19. The electronic device of claim 18, wherein the flexible alternative to glass is used in a device component selected from the group consisting of device substrates, touch panels, cover films and color filters.
Claims
1. A polyimide film prepared from a solution containing a polyamic acid, The polyamic acid is a carboxylic acid component comprising 100 mole % 4,4'-oxydiphthalic dianhydride (ODPA); A polyimide film comprising a diamine component comprising 90 mol % of 4,4'-[1,4-phenylenebis(1-methyl-ethylidene)]bisaniline (Bis-P) and 10 mol % of 2,2'-bis(trifluoromethyl)benzidine (TFMB).
2. 10. The polyimide film of claim 1 exhibiting an optical retardation at 550 nm that is less than 20 nm for a 10 μm film.
3. 3. A flexible replacement for glass in electronic devices comprising the polyimide film of claim 1 or 2.
4. An electronic device comprising the flexible substitute for glass of claim 3.
5. 5. The electronic device of claim 4, wherein the flexible alternative to glass is used in a device component selected from the group consisting of a device substrate, a touch panel, a cover film, and a color filter.
Citation Information
Patent Citations
Formed body of high-performance polyimide and its production
JP1992189827A
Polyimide soluble in organic solvent
JP1995173287A
Polyimide film
JP2010538103A
Copper-clad laminated plate having primer layer, and wiring board using the laminated plate
JP2012076363A
Polyimide film, polyimide varnish, product using polyimide film, and laminate
WO2016158825A1